Ultra-high-pressure extraction of plant polyphenols: a green and sustainable technology for food applications - Jing Wang; Lu Tang; Yuzhu Zhao; Feng Zhen; Xueting Sang; Bin Qu; Ming Wang (Biomass and Bioenergy, 2027)

Nutrient pumping triggers algal overgrowth in oligotrophic water bodies - Wenzhong Tang; Jie Liu; Zhibing Chang; Xiaoyue Zhang; Hong Zhang; Chengzhi Hu; Jiuhui Qu (Water Research, 2027)

Intelligent analysis and interpretation of aquatic organic matter fluorescence excitation-emission matrix - Yue Wang; Yucheng Wu; Shiqi Liang; Zihan Tang; Chunhai Wei; Huarong Yu; Fangshu Qu (Water Research, 2026)

Farrerol improves the maturation quality of porcine oocytes derived from small follicles associated with RAD51-related DNA repair responses - Lin Qi; Yingting Pan; Chaoqun Qu; Shuangyan Mo; Cuiting Peng; Hao Xie; Yulan Zhao; Yijie Tang; Wei Shen; Zhilong Chen; Zhonglin Tang (Theriogenology, 2026)

Adsorption Performance and Mechanism of Ni(II) by EDTA-Catalyzed Mg/Al Hydroxide-Modified Biochar - Weiping Sima; Jiang Qu; Qibin Xu; Hengjun Tang; Lin Wang (Water, Air, & Soil Pollution, 2026)

Large deformation mechanism of soft surrounding rock triggered by shallow-buried tunnel approaching fault: Insights from the geomechanical model test and numerical simulation - Mingyang Tang; Qiushi Liu; Fanmeng Kong; Yiguo Xue; Huimin Gong; Kang Fu; Huanqiang Luan; Jingkai Qu (Transportation Geotechnics, 2026)

Anomalously depleted δ2H signatures of tropical cyclone precipitation recorded in tree-ring lignin methoxy groups - Yabo Wang; Wenxin Li; Xiaohong Liu; Guobao Xu; Huhu Kang; Bingming Chen; Xianhui Tang; Jianjun Qu; Chong Jiang; Xin Song (Journal of Hydrology, 2026)

Global prioritization of PFAS in groundwater based on multi-scale evaluation of national and source-level data - Yan Zhou; Jinhong Tao; Weiling Tang; Fuyang Huang; Min Fan; Fei Liu; Faqin Dong; Shen Qu (Journal of Environmental Chemical Engineering, 2026)

Establishment of a novel brain cell line from grass carp (Ctenopharyngodon idella) with high transfection efficiency and CRISPR/Cas9-mediated genome editing capacity - Zi-Ling Qu; Tao Liu; Tang-Kai-Yuan Qin; Hua-Mei Yue; Ling Huang; Rui Ruan; Chang-Song Wu; Huan Ye; Chuang-Ju Li (Fish & Shellfish Immunology, 2026)

Antibiotic contamination in groundwater across major Chinese basins: Which compounds require priority control? - Weiling Tang; Baoni Chen; Fuyang Huang; Fei Liu; Faqin Dong; Shen Qu (Environmental Research, 2026)

Toward environmentally stable magnesium metal anodes via Bi interphase engineering for rechargeable magnesium batteries - Sitong Liang; Yuhang Chen; Xiaojin Lian; Zhimeng Tang; Lu Zhang; Xinwei She; Baihua Qu; Jingfeng Wang (Chemical Engineering Journal, 2026)

Local lattice strain in layered double hydroxides enhances flexoelectric effect for hydraulically driven water disinfection - Muke Lin; Shulin Zuo; Weiqi Liu; Zhipeng Zhang; Ye Chen; Rumeng Zhang; Wei Qu; Zhuoyun Tang; Dehua Xia (Chemical Engineering Journal, 2026)

Aluminum-based interfacial evaporator fabricated by picosecond laser synergistic high-temperature carbonization for multistage water-electricity cogeneration - Zhiliang Tang; Dongkai Chu; Peng Yao; Yongping Zhou; Shuoshuo Qu (Chemical Engineering Journal, 2026)

Exploration of low-carbon and sustainable concrete products: Using activated clay as supplementary cementitious materials - Yizhe Wang; Yucheng Fan; Fulin Qu; Yipu Guo; Zhiyu Luo; Kejin Wang; Hailong Ye; Rohit Tiwari; Zhuo Tang; Daniel C.W. Tsang; Wengui Li (Applied Clay Science, 2026)

Marek’s disease virus infection alters the composition of exosomes in chicken fibroblasts and promotes viral replication - Cuiping Song; Wenjing Yang; Jiepeng Wu; Xusheng Qiu; Lei Tan; Yingjie Sun; Ning Tang; Yang Qu; Ying Liao; Chan Ding (Veterinary Microbiology, 2026)

Iron-regulated crystallization in sensible-heat-driven glass-ceramics from molten lead-zinc smelting slag: Process-structure-property coupling and LCA quantification - Yibo Yang; Yusheng Tang; Hanguang Fu; Mengchen Xiao; Meichen Pan; Jixian Wu; Zhichuan Li; Zhe Tan; Zhixue Qu; Dean Pan; Xiaoguang Zhang (Process Safety and Environmental Protection, 2026)

Strain-specific fermentation reshapes aroma-active volatiles and antioxidant-related properties of soy protein isolate-based plant milk - Hanhan Shi; Jiaming Li; Tanxu Tang; Tianzhi Qu; Jian Chen; Anqi Chen; Jianghua Li (Food Bioscience, 2026)

Immobilized microbial reduce nitrogen loss during composting: Enhancement of ammonia assimilation and nitrification pathways - Yiqi Yin; Yutong Tang; Wenfang Gao; Fengting Qu; Zimin Wei; Caihong Song (Environmental Research, 2026)

Spatiotemporal patterns and potential risks of heavy metal(loid)s in surface seawater of the Liaohe Estuary coastal area in summer during 2021–2023 - Pengfei Feng; Jingyang Tang; Weiyan Duan; Limei Qu; Yingbo Duan (Regional Studies in Marine Science, 2026)

Three new prenylated phoroglucinols from Hypericum henryi with anti-neuroinflammatory activities - Chang-Hao Luo; Mi Yang; Ming-Gen Tang; Jing-Yu Luo; Jia-Yi Qu; Chang-Wang Luo; Ye-Juan An (Phytochemistry Letters, 2026)

Micritization mechanism in penecontemporaneous carbonate rocks: coupled C − Ca cycles and constraints from diagenetic environments - Yunfeng Zhang; Menghao Zhu; Wen Yan; Haizhou Qu; Kexin Guo; Weihai Xu; Xiyang Zhang; Fei Tan; Yu Tang; Rui Wang; Guanghui Wu; Shuai Huang (Geochimica et Cosmochimica Acta, 2026)

Towards near-zero emission methanol engines: Coupled mechanisms of pollutant formation and combustion–catalysis synergistic control - Jia Tang; Bin Guan; Lei Zhu; Shiying Chang; Jiangli Ma; Rong Wang; Dongxia Yang; Tiankui Zhu; Hanshi Qu; Bingqian Tan; Zheng Huang (Fuel, 2026)

Emeishan basalt’s contribution to heavy metals in topsoil (notably cadmium) in Southwest China from soil geochemistry evidence - Fang Yang; Liang Tang; Yang Li; Bo Cheng; Tim T. Werner; Lingfei Qu; Ke Cheng; Aiming Zhang; Junbo Wang; Guikai Li (Acta Geochimica, 2026)

Potential roles of MyoD in promoting myogenesis and muscle growth in Fenneropenaeus chinensis - Xia Lu; Zebin Zhang; Nan Jiang; Yongzheng Tang; Fangrui Lou; Yan Liu; Tingjin Lü; Xuewei Qu (Journal of Oceanology and Limnology, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Pulmonary effect of 2D MXenes in mice: Immune cell responses and disrupted hematopoiesis - Gang Tang; Min Li; Jiexia Cheng; Ziniu Wang; Guangxuan Wang; Jianbo Shi; Jonathan W.C. Wong; Jie Gao; Dou Wang; Guohao Zhang; Li Zeng; Yanhua Wang; et al. (NanoImpact, 2026)

Integrating GNSS and GRACE/GRACE-FO with GCV joint inversion for improved terrestrial water storage estimation in California - Peinan Chen; Wei Qu; Xingyou Tang; Jiuyuan Li; Haopeng Zhang (Journal of Hydrology, 2026)

Corrigendum to “Towards near-zero emission methanol engines: Coupled mechanisms of pollutant formation and combustion–catalysis synergistic control” [Fuel 418 (2026) 138729] - Jia Tang; Bin Guan; Lei Zhu; Shiying Chang; Jiangli Ma; Rong Wang; Dongxia Yang; Tiankui Zhu; Hanshi Qu; Bingqian Tan; Zhen Huang (Fuel, 2026)

Nitrogen-vacancy-regulated plasmonic Schottky interfaces on Ag/C3N5 for ultrafast oxygen activation and solar-driven antibiotic degradation - Kaizhou Huang; Wei Qu; Tenghui Jin; Yutong Xie; Zhuoyun Tang; Ming Su; Ping Zhang; J. Paul Chen (Chemical Engineering Journal, 2026)

MSC-sEV Promote Regeneration of Cochlear Spiral Ganglion Neurons and Myelin Sheaths in 3D Culture System - Yunyou You; Anning Chen; Jiaxi Qu; Yiman Guo; Jing Pan; Taolue Yu; Fan Shu; Jie Tang; Hongzheng Zhang (Neuroscience Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Lycopene ameliorates swainsonine-induced autophagy in rat renal tubular epithelial cells via the endoplasmic reticulum stress UPR pathway - Pan Wang; Lihui Tang; Liwen Yang; Congcheng Zhang; Hai Yin; Siqi Hou; Yin Shao; Yingying Qu; Hao Lu (Research in Veterinary Science, 2026)

Splicing factor SC35 inhibits Nosema bombycis proliferation by regulating the alternative splicing of Bmupp1 - Qiong Yu; Qingsheng Qu; Shiyi Lu; Pingyang Wang; Li Sui; Jie Cheng; Xudong Tang; Ping Qian (Journal of Invertebrate Pathology, 2026)

First mapping of subsurface soil temperature profiles by integrating diurnal cycles of microwave and thermal infrared observations - Dabiao Chen; Huazhu Xue; Tianjie Zhao; Yuyang Xiong; Ning Li; Jingyao Zheng; Yipeng Cao; Yu Bai; Songbo Qu; Ling Yao; Tang Liu; Chi Wang; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Mineral dissolution products drive anammox nitrogen removal via sludge aggregation - Fan Feng; Jingyu Liu; Caiyan Qu; Xi Tang; Di Wu; Chong-Jian Tang; Liyuan Chai (Environmental Research, 2026)

Preparation, properties of bond energy-driven LKCC sequential drug-releasing hydrogel and its application in biofilm-infected wound repair - Jiangchuan He; Huan Wang; Yunhe Zheng; Yu Huang; Ting Wang; Hanchao Zhou; Kailai Liu; Yuchen Zhang; Jinpeng Wen; Jingya Qu; Pengchong Wang; Ling Liu; et al. (Chemical Engineering Journal, 2026)

An adhesive chitosan microneedle patch incorporating a Sargassum-derived polysaccharide for skin repair - Qianqian Ouyang; Hongjiao Qu; Weiyan Quan; Yongkai Tang; Xufeng Zhu; Luming Deng; Xian Xie; Kefeng Wu (Carbohydrate Polymers, 2026)

Root morphological strategies enhance growth of Cunninghamia lanceolata and Schima superba under nitrogen stress in intercropping systems - Xiao-Li Yan; Cong Cheng; Yunhao Xu; Jiaxiang Yu; Zhaozhao Wang; Yanru Wang; Xinghao Tang; Pengfei Wu; Xiangqing Ma; Lu-Ping Qu (Plant and Soil, 2026)

Genetic structure and identification of divergent genomic regions of Solen grandis from three geographic populations based on whole genome resequencing - Fangrui Lou; Yaoran Fan; Yatong Yao; Wei Chen; Baojun Tang; Yinquan Qu; Tianxiang Gao; Hanfeng Zheng (Frontiers in Marine Science, 2026)
The grand jackknife clam, Solen grandis , is a crucial mariculture bivalve with high economic value. To investigate the genetic variation of S. grandis in China, the whole-genome resequencing was carried out on 81 individuals from three S. grandis geographical populations (Huludao [HLD], Rizhao [RZ], and Dongtai [DT]) to develop the genome-wide SNPs. Generally, all three populations indicated low genetic diversity. For each population, the observed heterozygosity ( H O ) ranged from 0.097 to 0.101, the expected heterozygosity ( H E ) from 0.105 to 0.109, the number of effective alleles ( N e ) from 1.329 to 1.343, nucleotide diversity ( π ) between 0.0107 and 0.0111, the polymorphism information content (PIC) from 0.156 to 0.160, and the inbreeding coefficient ( F IS ) values of 0.042 to 0.053. Meanwhile, the fixation index pairwise ( F ST ) values among the three S. grandis populations ranged from 0.008 to 0.023, which were low differentiation. Additionally, population structure analysis revealed that the RZ and DT populations first clustered together and were further grouped with the HLD population. Moreover, the genome-wide outlier analysis identified 32 candidate selected regions with a total size of 5.50Mb, as well as 10 candidate genes including ACE (Angiotensin-converting enzyme), KIAA1161 (Myogenesis regulating glycosidase), CES1 (Carboxylesterase 1), RPS13 (Ribosomal protein S13), APOD (Apolipoprotein D), PPP1R13B ( Protein phosphatase 1 regulatory subunit 13B ), and CHDH ( Choline dehydrogenase ), etc. Overall, this study enriches the genetic resources of S. grandis and improves our understanding of its population genetic structure and selection signatures, providing a useful reference for future genetic resource conservation and management.

Numerical Study on the Crushing Failure of Sea Ice Against a Vertical Structure Using the S-ALE Method - Yukui Tian; Yunjing Zhao; Haidian Zhang; Chaoge Yu; Yan Qu; Haoyang Yin; Shaowei Tang (Journal of Marine Science and Engineering, 2026)
The crushing failure of sea ice is a critical design issue for polar offshore structures and ship structures because ice-induced loads may generate pronounced local damage and dynamic responses. Accurately modelling this process remains challenging because ice crushing involves localized fragmentation, crack propagation, rubble accumulation, and repeated contact release. This paper presents a controlled numerical sensitivity study of level-ice crushing against a vertical structure using a coupled LS-DYNA framework that combines the Structured Arbitrary Lagrangian–Eulerian (S-ALE) formulation with the Cohesive Element Method (CEM). The study focuses on a benchmark-scale indentation configuration and examines how mesh topology, mesh size, and imposed indentation velocity affect the predicted fracture morphology and load-time histories. The results show that random triangular meshes better reproduce stochastic fragmentation and lateral flaking than regular triangular or quadrilateral meshes, while finer meshes reduce excessive load oscillations and provide more stable force histories. The velocity study indicates a transition from gradual crushing and fragment retention at lower velocities to more rapid brittle chipping and stronger dynamic fluctuations at higher velocities. A benchmark-level comparison with published ice-indentation simulations shows that the predicted peak line load is of the same order of magnitude as reference results. The proposed framework is therefore useful for investigating numerical sensitivities and failure-mode trends in ice-crushing simulations, although final design-load application requires further calibration and formal mesh-independence assessment.

Effects of various environmental factors on the quality of low-salt shrimp sauce during storage and its underlying mechanisms revealed by metabolomics - Wenhui Qu; Luying Tang; Weijia Liu; Ruoshu Li; Lihao Wang; Qing Kong; Yunqi Wen; Changhu Xue (Food Chemistry, 2026)

An ROS-scavenging dual-network hydrogel for diabetic bone regeneration - Zhengyu Cai; Weizhe Xu; Qingxiang Zhang; Xingwu Zhou; Jiang Zeng; Zhiyong Wang; Peng Deng; Ping Sun; Fan Tang; Xing Jiang; Moyuan Qu; Qianming Chen (Chemical Engineering Journal, 2026)

Metabarcoding Chironomid Pupal Exuviae Enables Scalable Biomonitoring With High Comparability to Morphotaxonomy - Wu Han; Chu‐Ming Zhang; Cheng Qian; Tsz‐Ying Chan; Thilina S. Nimalrathna; Bai‐an Lin; Xiao‐Long Lin; Hong‐Qu Tang; Peter S. Cranston; Mathew Seymour (Molecular Ecology, 2026)
Conventional morphotaxonomy‐based biomonitoring requires modernization to enable timely assessments in the face of an accelerating freshwater biodiversity crisis. The Chironomid Pupal Exuviae Technique (CPET) is an established biomonitoring approach with considerable potential for integration with molecular methods, as the shed pupal skins of emerging adults provide a source of DNA. We tested the performance of DNA metabarcoding for detecting species richness, recovering beta‐diversity patterns and assessing biodiversity responses to environmental gradients using 15 mock communities and 12 natural chironomid pupal exuviae samples collected from Hong Kong streams. Additionally, the effects of primer choice were assessed by comparing a chironomid‐specific primer set (COI‐S) against a universal, highly degenerate primer set (COI‐V). Our results show that both primer sets achieved high species detection rates in mock communities (86% and 84%, respectively) and consistently recovered predefined community dissimilarities. In natural community samples, however, only COI‐S produced beta‐diversity patterns significantly congruent with that of the morphological dataset (Procrustes r = 0.74, p = 0.003). Both metabarcoding datasets effectively captured seasonal community shifts and demonstrated greater sensitivity to environmental gradients than traditional morphological identification. Notably, the COI‐S dataset explained the highest proportion of community variation (adjusted R 2 = 44.3%), along the environmental gradient, outperforming both the morphotaxonomy (32.5%) and the COI‐V (29.0%) analyses. Here we propose Meta‐CPET, an integrated framework that combines the ecological relevance of CPET with the efficiency, scalability, and resolution of DNA metabarcoding. Our findings show that bulk‐sample metabarcoding enables practical, standardized and large‐scale freshwater biomonitoring while maintaining strong comparability with conventional methods.

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Flash-spun composite fiber membranes for broadband electromagnetic absorption and multifunctionality - Daixuan Gong; Xincheng Wang; Meijie Qu; Shuhui Li; Ping Tang; Yuezhen Bin (Chemical Engineering Journal, 2026)

The Analysis of miRNA–mRNA Network Regulation Revealed the Mechanism of Different Drugs-Induced Constipation in Mice - Yu Zhan; Yong Wen; Jing-hui Qu; Xue-gui Tang (Biochemical Genetics, 2026)

Sources and transportation of mining metals to soil: A case study from the Lala mining area, Southwest China - Fang Yang; Lei Xu; Liang Tang; Li Dai; Xuemin Liu; Tim T. Werner; Lingfei Qu; Xuefeng Liao; Yang Li; Junbo Wang (Acta Geochimica, 2026)

Decoupled Global Trends in Zinc Deficiency–attributable Burden (GBD CRA) and Depressive Disorders, 1990–2021: a GBD 2021 Analysis - Chenqi Li; Hongtao Lu; Qicheng Zhou; Yicui Qu; Mengyu Cai; Wenjing Shi; Yinyin Zhang; Gen Miao; Yuxiao Tang; Hui Shen; Biao Gao (Biological Trace Element Research, 2026)

Anammox dominated As(V/III) speciation during long-term anaerobic conditions - Taicong Liu; Shuting Tang; Yingpeng Sun; Zhongtao Lao; Daijie Chen; Ming Ao; Haojie Qu; Chao Jin; Liying Lan; Roland Bol; Miaoyue Zhang; Yingjie Cao; et al. (Soil Biology and Biochemistry, 2026)

Development of naringenin-loaded foxtail millet prolamin nanoparticles modified with hyaluronic acid: Characterization, stability, and bioaccessibility - Wen Zhang; Wenjing Liang; Zhizhe Zhang; Jiaxi Wang; Lijun Pan; Ao Qu; Runyan Wang; Yuying Tang; Pei Zhao; Shuaishuai Gao; Zijian Wu (Food Chemistry, 2026)

Analysis of phenomics, metabolomics and transcriptomics reveals the differences in fruit quality between on-tree bagged and non-bagged apples - Yuan Zhao; Yinxin Tang; Ritao Qu; Jing Guo; Yufei Gu; Min Xiao; Chengwei Wu; Qi Pan; Manyu Zhang; Yuandi Zhu (Food Chemistry, 2026)

Metabolic reprogramming-based therapeutic strategy for refractory deep bacterial keratitis with antibiotic resistance - Miaomiao Chi; Wenyue Xie; Long Lin; Guoguo Tang; Yang Zhai; Yinghan Zhao; Yiming Han; Shaofeng Gu; Ying Li; Yaning Zhao; Chengjie Feng; Yi Qu; et al. (Chemical Engineering Journal, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Recycling waste claystone into value-added and eco-friendly cementitious materials for concrete industry decarbonisation - Fulin Qu; Juanjuan Ren; Like Tang; Wengao Liu; Kejin Wang; Wengui Li (Journal of Cleaner Production, 2026)

The sequestration of metal nanoparticles in the liver: A trade-off between density and degradability - Junjie Ma; Li Zeng; Yaquan Liu; Shunhao Wang; Min Li; Linlin Yao; Gang Tang; Ziniu Wang; Jiexia Cheng; Qi Wu; Guangxuan Wang; Chunzhen Shi; et al. (Journal of Environmental Sciences, 2026)

RSM-based development and optimization of a novel fracture sealing material for secondary grouting in extraction boreholes - Junxiang Zhang; Yijian Guo; Bo Li; Yadong Bian; Shumin Ding; Lina Qu; Zhenfeng Wang; Yaocai Tang; Pan Chen (Fuel, 2026)

Modification of β-lactoglobulin by glycation, high-pressure microfluidization and EGCG binding: Enhanced emulsifying and antioxidant properties - Rui Wang; Qingchun Zhang; Juan Qu; Jianfei He; Christos Ritzoulis; Weilin Liu; Wei Tang; Jianhua Liu (Food Research International, 2026)

Using machine learning method to predict the quality of fermented krill sauce based on the freshness of Antarctic krill - Wenhui Qu; Luying Tang; Ruoshu Li; Weijia Liu; Xiaoming Jiang; Qing Kong; Yunqi Wen; Changhu Xue (Food Chemistry, 2026)

The efficient ethane oxychlorination to ethylene on Cu Zn LDO through confinement-interface synergy - Kunhao Bi; Baosen Tang; Wei Cui; Shaoqing Qu; Weizhen Sun; Ling Zhao (Chemical Engineering Journal, 2026)

Glycine Drives IMP Production in Hybrid Bream (Megalobrama Amblycephala ♀ × Culter Alburnus ♂) Via Concerted Action: Activating glycyl-tRNA Synthetase and Fueling the Pentose Phosphate Pathway - Zhehua Xu; Weiting Zhang; Ruijie Zhan; Jiefan Zhou; Man Chen; Yonghua Zhou; Fufa Qu; Rong Zhou; Shaochun Liu; Shenping Cao; Jianzhou Tang; Zhen Liu (Marine Biotechnology, 2026)

Establishment and application of efficient protoplast isolation and transformation system from leaves of multi-genotype poplars - Fang Tang; Shanchen Zhong; Huishan Qu; Shutang Zhao; Jianjun Hu (Plant Science, 2026)

Resistance mechanisms and fitness outcomes of tetraniliprole, one novel diamide insecticide, in a near-isogenic strain of Spodoptera litura (Lepidoptera: Noctuidae) - Peng Lu; Ren Li; Xiao Guo; Juan Tang; Yilu Tong; Shengran Zhang; Qi Su; Cheng Qu; Ran Wang (Pesticide Biochemistry and Physiology, 2026)

Overexpression of cytochrome P450 gene CYP402C18 contributes to the detoxification of dimpropyridaz, one novel pyridazine pyrazolecarboxamide insecticide, in the whitefly Bemisia tabaci Mediterranean cryptic species - Juan Tang; Ren Li; Zehua Wang; Peng Lu; Cheng Qu; Ran Wang (Pesticide Biochemistry and Physiology, 2026)

Long-term effects of pH and salinity on performance and bacterial community of bioaugmented sequencing batch reactor for treatment of nitrogen-containing organic pollutants - Zhaojian Song; Qidong Tang; Haiqian Wei; Hao Zhou; Yuanyuan Qu; Jingjing Zhan; Xuwang Zhang (Journal of Water Process Engineering, 2026)

Construction of hierarchical Zn-HHTP/LDH heterostructures for selective and enhanced lithium extraction via capacitive deionization - Chang He; Guoqiang Zhong; Jun Zhang; Ruifeng Song; Yanzhou Tang; Junhao Chen; Rengui Weng; Xusheng Wang; Zhang Yan; Yang Qu; Wei Lu; Zhuwu Jiang (Desalination, 2026)

The enrichment and metabolic adaptation of autotrophic denitrifiers in pyrite-induced biofilms enhances TN removal and reduces carbon demand in A2/O systems - Huize Guan; Caiyan Qu; Jingyu Liu; Sheng Hu; Xi Tang; Di Wu; Chong-Jian Tang (Chemical Engineering Journal, 2026)

Long Non-Coding RNA PVT1 Inhibits Apoptosis Through the miR-30d-5p/CaMKIIδ Axis in Hypoxic–Ischemic Brain Injury - Fengyan Zhao; Junyan Liu; Zihong Xiong; Lingyi Huang; Yuanyuan Zhao; Shiping Li; Junjie Ying; Qian Liu; Shaopu Wang; Xiaojuan Su; Jun Tang; Yi Qu; et al. (Molecular Neurobiology, 2026)

Spatiotemporal heterogeneity of magnetic enhancement mechanisms in aeolian deposits on the southern Tibetan Plateau: Implications for paleoclimatic reconstruction in mountain-basin systems - Haoyu Wang; Junhuai Yang; Wenxi Qu; Linkai Wang; Canyi Zhang; Xin Liu; Jinmeng Tang; Fuyuan Gao; Zixuan Chen; Shuyuan Wang; Yijiao Fan; Duo Wu (Journal of Geographical Sciences, 2026)

Factors contributing to elevated springtime surface ozone levels in eastern China - Fanghe Zhao; Yuhang Wang; Lewis Gregory Huey; Shengjun Xi; Young Ro Lee; Wei Song; Xinming Wang; Jianhui Tang; Kezhen Chong; Hang Qu (Science of The Total Environment, 2025)

Two new compounds from the roots of Mirabilis jalapa L. and their cytotoxic activity in vitro - Xiao-Mei Yan; Tian-Tian Qu; Jie Luan; Hou-Run Zhang; Xiang-Qin Tang; Xiao-Xu Bi; Ying Wang; Bing Chen; Jiang-Bo He (Phytochemistry Letters, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Multi-modification of food protein: Design, structural transformation, and functional application - Wei Tang; Juan Qu; Yixuan Zhang; Jiahui Chen; Weilin Liu; Jianfei He; Jianhua Liu (Food Chemistry, 2025)

Microplastics as vectors for microcystin-LR: Enhanced bioavailability, oxidative damage, and immune dysregulation in zebrafish spleen - Wang Lin; Xixun Zhou; Yunyun Zeng; Xiaojie Li; Fufa Qu; Jianzhou Tang (Fish & Shellfish Immunology, 2025)

Performance enhancement strategies for lithium-based battery electrodes via covalent organic frameworks: A review of recent advances - Waheed Ahmad; Muhammad Tahir; Batoul Bibi; Liang He; Hui Tang; Longbing Qu; Fazal Ul Nisa; Mizna Naseem; Habib Ullah; Iram Abdul Ghafar; Saira Manzoor; Yihao Long; et al. (Chemical Engineering Journal, 2025)

The behavior and mechanism of novel clustered phosphate ester derivative in simultaneously enhancing the flame retardancy and mechanical properties of thermoplastic polyurethanes - Zeyu Li; Lijun Qian; Wang Xi; Lijie Qu; Wei Tang (Chemical Engineering Journal, 2025)

Heterogeneous phototransformation of o,p′-DDT in four typical Chinese basins: Effects of suspended particulate matter composition and toxicity evaluation of intermediates - Junyan Wei; Wenqian Cao; Hao Chen; Xiaosheng Tang; Zongli Huo; Feng Zhu; Zunyao Wang; Ruijuan Qu (Chemical Engineering Journal, 2025)

Negative-pressure induced controllable foaming reaction for ultralight and flame-retardant phenyl-containing silicone rubber foam nanocomposites modified with low content of graphene oxide - Shuai-Chi Liu; Yun-Hao Qu; Dun-Peng Bao; De-Mei Kong; Zhi-Hao Xu; Zuan-Yu Chen; Yang Li; Jie-Feng Gao; Yong-Qian Shi; Pingan Song; Guo-Dong Zhang; Long-Cheng Tang (Chemical Engineering Journal, 2025)

Critical factors for carbon fixation efficiency in semiconductor-biohybrid systems: insights from a meta-analysis - Diantong Li; Ziyang Tang; Chenchen Wang; Jie Mao; Yaohui Bai; Jiuhui Qu (Bioresource Technology, 2025)

Spatiotemporal analysis of habitat quality and carbon storage in the Yanni Valley, Southwest China - Jinkai Gu; Xingle Qu; Wanchi Li; Shengjian Xiang; Qingwan Li; Shunbin Wang; Guoyong Tang (Tropical Ecology, 2025)

BS-D275: A novel locus on the chromosome arm 2DS governing branched spike development in wheat - Yunfeng Qu; Yongkang Ren; Jinghuang Hu; Yi Liu; Dan Qiu; Yahui Li; Qiuhong Wu; Miao He; Qing Guo; Yu Sun; Wenze Yan; Zhaohui Tang; et al. (Theoretical and Applied Genetics, 2025)

A comprehensive analysis of stroke risk factors and development of a predictive model using machine learning approaches - Songquan Xie; Shuting Peng; Long Zhao; Binbin Yang; Yukun Qu; Xiaoping Tang (Molecular Genetics and Genomics, 2025)

Correction to: Integrative single-cell and bulk RNA-seq analysis identifies lactylation-related signature in osteosarcoma - Zhou Xie; Xiao Qu; Jun Zhang; Yanran Huang; Runhan Zhao; Dagang Tang; Ningdao Li; Zhule Wang; Xiaoji Luo (Functional & Integrative Genomics, 2025)

Integrative single-cell and bulk RNA-seq analysis identifies lactylation-related signature in osteosarcoma - Zhou Xie; Xiao Qu; Jun Zhang; Yanran Huang; Zhao Runhan; Dagang Tang; Ningdao Li; Zhule Wang; Xiaoji Luo (Functional & Integrative Genomics, 2025)

Visible light-mediated persulfate activation by magnetite: Wavelength-specific radical generation and bisphenol AF transformation pathways - Ying Zhang; Cheng Qin; Jiajia Pang; Xiaoxue Pan; Rehab Khaled Mahmoud; Xiaosheng Tang; Zunyao Wang; Ruijuan Qu (Science of The Total Environment, 2025)

Western Pacific subtropical high regulated the spatiotemporal pattern of East Asian summer monsoon precipitation during the Holocene - Linkai Wang; Junhuai Yang; Fuyuan Gao; Haoyu Wang; Canyi Zhang; Wenxi Qu; Jianye Li; Jinmeng Tang; Xin Liu; Yan Liu; Lai Zhao; Shuyuan Wang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Soil Water Accounting Network (SWAN): a novel neural network for modeling conceptual hydrological processes - Zheng Fang; Simin Qu; Ziheng Li; Qiongfang Li; Peng Shi; Yiqun Sun; Xiaoqiang Yang; Han Tang; Junfang Zhang; Zhengxian Zhu; Hongshi Wu; Weimin Bao (Journal of Hydrology, 2025)

Tailored esterification of Geraniin for optimal anti-isomerization and anti-oxidation activities - Junxia Jiang; Pengyin Li; Hongting Ji; Zhenpei Liang; Aoxue Tang; Xinyi Lu; Tong Li; Yang Qu; Jiamu Kang; Tian Li; Weimin Zhang (Food Research International, 2025)

Non-volatile metabolite profiles and taste quality of Pu-erh raw tea on different storage years by metabolomics and 1H qNMR - Long Chen; Yaqin Long; Hao Qu; Ziwen Luo; Lixue Long; Hongyun Chen; Qiang Chen; Song Tang; Linbo Chen (Food Research International, 2025)

Radial oxygen loss of Typha latifolia outperforms microbial effects in heavy metal(loid) stabilization - Taicong Liu; Liying Lan; Yuanyuan Li; Daijie Chen; Ming Ao; Shuting Tang; Haojie Qu; Chao Jin; Miaoyue Zhang; Roland Bol; Jean Louis Morel; Zhihong Xu; et al. (Environmental Research, 2025)

Synergistic air pollution and CO2 emission reduction in China's iron and steel industry based on real-time monitoring data - Ling Tang; Qing Yu; Jiabao Qu; Ruxing Wan; Min Jia; Shuangyue Qian; Song Lv; Jieyi Li; Shuo Qi (Environmental Pollution, 2025)

Cost-effective n-type liquid flow thermocells with giant ionic thermopower and power density through solvation entropy engineering for low-grade heat harvesting - Zhuo Liu; Zhongyi Li; Ming Qu; Huidong Yang; Junxiang Tang; Fanghao Zhong; Xiang Wei; Yangfan Song; Zhenfei Liu; Hongwei Chen (Chemical Engineering Journal, 2025)

Visible light-triggered synergistic antibacterial coating based on a PDMS/porphyrin graft copolymer - Jiujiang Ji; Wenting Li; Jingsong Lu; Diane Tang; Enjian He; Mingrui Wu; Ruixiang Qu; Yongfa Zhu; Zhijun Ma; Guojun Liu; Yen Wei (Chemical Engineering Journal, 2025)

In situ engineering of conductive MOF/LDH heterojunction nanosheet arrays for high-efficiency lithium extraction via capacitive deionization - Chang He; Guoqiang Zhong; Rengui Weng; Xusheng Wang; Jun Zhang; Ruifeng Song; Yanzhou Tang; Junhao Chen; Zhang Yan; Yang Qu; Zhuwu Jiang (Chemical Engineering Journal, 2025)

A keypoint detection-based approach for real-time aggressive behavior identification in goats - Hongchun Qu; Ansong Leng; Yutong Deng; Xiuping Yin; Xiaoming Tang; Shidong Zhai (Applied Animal Behaviour Science, 2025)

Zinc Ameliorates LPS-Induced Depressive-Like Behaviors Via Modulating Microglial Polarization - ChenQi Li; Gen Miao; Wenjing Shi; Yangjuan Gu; Weiwei Li; Mengyu Cai; Yicui Qu; Yuxiao Tang; Hongtao Lu; Hongxia Li; Hui Shen (Biological Trace Element Research, 2025)

Functional characterization of ampd1 and its SNPs in the muscle IMP synthesis of hybrid bream (Megalobrama amblycephala ♀ × Culter alburnus ♂) - Zhehua Xu; Qinqin Xiao; Mingyu Zhang; Yimiao He; Qianting Zheng; Junchi Zhao; Anli Zuo; Jianzhou Tang; Yonghua Zhou; Shenping Cao; Fufa Qu; Zhen Liu (Aquaculture, 2025)

Cuproptosis is involved in small intestinal toxicity in the paraffins during pregnancy - Juan Tang; Zemin Xu; Mengna Jiang; Chao Luo; Xiaoyan Li; Yuling Jiang; Yi Qu; Jialing Ruan; Xiaoke Wang; Meihua Zheng; Wing-Cheung Law; Xinyuan Zhao (Toxicology Letters, 2025)

Corrigendum to “WWOX attenuates the progression of gallbladder cancer by suppressing cellular glycolysis through the modulation of the P73/HIF-1a signaling pathway” [Tissue Cell 95 (2025) 102885] - Bo Tang; Qi-Cai Qu; Dong-Yun Cun; Xia-Wei Yang; Kun Su; Ren-Chao Zou; Tao Wang; Lian-Min Wang; Tao Wu; Dong Wei; Qiu-Hong Wang (Tissue and Cell, 2025)

Integrated phosphorus removal and recovery using MgO2-magnetic biochar: A circular approach combining fenton chemistry and soil fertility enhancement - Zhibo Zhang; Chuchu Feng; Miaoqu Wang; Kuok Ho Daniel Tang; Ronghua Li; Guangzhou Qu; Junting Pan (Journal of Environmental Chemical Engineering, 2025)

The effect of soil organic matter on the photodegradation of polycyclic aromatic hydrocarbons: Experimental analysis and excited-state theory calculations - Junyun Huang; Zhengnan Tu; Xiaolei Teng; Xiaosheng Tang; Moustafa M.G. Fouda; Hanan Sayed Abdel-Rahman; Ruijuan Qu (Journal of Environmental Chemical Engineering, 2025)

Intestinal metabolomic profiling provides insights into the molecular mechanisms for hyperuricemia-induced intestinal barrier dysfunctions in a hyperuricemia mouse model - Hailong Li; Qingli Zhang; Tingting Tang; Lei Zhu; Qu Chen; Haili Zhang; Yan Zhang; Zichu Zhao; Di Xiao; Xinlei Sha; Jingrong Mu; Jingjing Kong (Food and Chemical Toxicology, 2025)

Design and performance of moisture-responsive piezoelectric nanogenerators based on electrospinning poly(vinylidene fluoride) films - Shuhui Li; Meijie Qu; Yonghao Chen; Ping Tang; Xiaobin Liang; Ken Nakajima; Yuezhen Bin (Chemical Engineering Journal, 2025)

Gradient multi-component interphase enabling highly reversible magnesium metal anode in fluorinated alkoxyborate-based electrolytes - Yuhang Chen; Yiming Zhang; Zhimeng Tang; Zhenyu Zhang; Le Tong; Xuemin Gan; Xing Shen; Guangsheng Huang; Qian Li; Baihua Qu; Fusheng Pan; Jingfeng Wang (Chemical Engineering Journal, 2025)

The role of pyrite in promoting anammox performance under Cr(VI) stress: not only extracellular reduction but also microbial enhancement - Fan Feng; Caiyan Qu; Wenming Wang; Xiaomei Jiang; Xi Tang; Chong-Jian Tang (Chemical Engineering Journal, 2025)

Isolation and characterization of minor monoterpene glycosides from the roots of Paeonia lactiflora - Yongliang Ding; Dan Han; Qian Tang; Lijuan Wang; Zhongtang Qu (Biochemical Systematics and Ecology, 2025)

Improvement of isolation and drug testing methods for Corynebacterium spp. in clinical specimens of granulomatous mastitis - Fang Liu; Yewei Yuan; Ruiyang Wu; Ninghua Tang; Kehua Chen; Kui Fan; Wei Cheng; Qu Pan (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Small-molecule fluorescent probes for imaging intracellular amyloid toxicity induces ferroptosis via HClO fluctuation in Alzheimer's disease - Wenhui Ma; Bingbing Tang; Han Zhang; Yixin Qu; Jinfeng Luan; Kelong Wang; Wenbo Chen; Xijuan Wang; Xinran Liu; Hongyan Zhao; Haixia Li; Ming Luo; et al. (Analytica Chimica Acta, 2025)

Evaluating the influence of double-channel inclined spreading blades on the effect of fertiliser granule spreading: DEM modelling and simulations - Wenqi Zhou; Qu Lu; Yao Wang; Han Tang; Jinwu Wang; Yijia Wang; Xiaobo Sun (Biosystems Engineering, 2025)

Electrically tuning low-pressure membrane surface charge for highly efficient Cr(VI) removal from drinking water - Jiaqi Bai; Lie Liu; Xiaoqiang An; Qingwen Tang; Huachun Lan; Huijuan Liu; Jiuhui Qu (Water Research, 2025)

Multi-omics profiling reveals infectious bursal disease virus-induced alterations in gene expression and metabolism in chicken bursa of fabricius - Cuiping Song; Siyu Li; Yanmei Yuan; Wei Gao; Xusheng Qiu; Lei Tan; Yingjie Sun; Ning Tang; Yang Qu; Ying Liao; Chan Ding (Veterinary Microbiology, 2025)

Crystal facet engineering of {100}-dominant Co-impregnated cubic CeO₂ catalysts for enhanced peroxymonosulfate activation and bisphenol A degradation - Zhibo Zhang; Yuan Luo; Wenxin Zhang; Mengjiao Ji; Ronghua Li; Kuok Ho Daniel Tang; Guangzhou Qu; You Li (Journal of Hazardous Materials, 2025)

Permeability of marine gas hydrate-bearing sediments considering effective stress and particle size distribution: A theoretical model - Yihan Shang; Gang Lei; Jiadi Tang; Jiangtao Qu; Fulong Ning (Computers and Geotechnics, 2025)

Dielectrically optimized Ni/CeO2/CNT catalysts for low-power and stable microwave-assisted dry reforming of methane - Tingting Wang; Xiaojun Li; Fengjuan Liu; Bei Liu; Xinkang Peng; Zhiheng Wang; Ning Qu; Jie Kong; Zhenchen Tang; Feng Zeng; Han Lin; Xiaohua Lu; et al. (Chemical Engineering Journal, 2025)

Ozone Stress Alters Rhizosphere Soil pH, Enzymes and Microbial Communities of Acer negundo and A. Mono Maxim - Qin Wang; Meng Zhang; Zhaoxin Tang; Qingqing Yang; Jianwei Ma; Laiye Qu (Journal of Soil Science and Plant Nutrition, 2025)

Photochemical transformation and interaction of octachlorodibenzofuran (OCDF) with microplastics in suspended particulate matter-water system - Xiaolei Teng; Mengqiang He; Jianqiao Xu; Xiaosheng Tang; Qing Zheng; Zunyao Wang; Ruijuan Qu (Water Research, 2025)

WWOX attenuates the progression of gallbladder cancer by suppressing cellular glycolysis through the modulation of the P73/HIF-1α signaling pathway - Bo Tang; Qi-cai Qu; Dong-yun Cun; Xia-wei Yang; Kun Su; Ren-chao Zou; Tao Wang; Lian-min Wang; Tao Wu; Dong Wei; Qiu-hong Wang (Tissue and Cell, 2025)

One-billion-year-old eukaryotic algal fossil Arctacellularia from North China and its implications for the evolution of pre-Cryogenian filamentous multicellularity - Rui Huang; Guangjin Li; Jiayue Wang; Qing Tang; Mingyang Qiu; Qian Chen; Hanzhi Qu; Chengxi Wu; Wenfei Cui; Xianqin Yan; Chuanming Zhou; Xunlai Yuan; et al. (Precambrian Research, 2025)

The combination of FLI, ITS, pFF, and citrate improves the developmental potential of gilt oocytes during in vitro maturation - Zhilong Chen; Caiyong Zhang; Chao Yan; Cuiting Peng; Hao Xie; Yingting Pan; Lin Qi; Chaoqun Qu; Yulan Zhao; Zhonglin Tang (Animal Reproduction Science, 2025)

Habitat‐Forming Species: Buffers or Amplifiers for Mutualistic Organisms in Response to Climate Change? - Junmei Qu; Zhixin Zhang; Shaobo Ma; Yaqi Wang; Xiaoyu Tang; Jianping Yin; Geng Qin; Qiang Lin (Journal of Biogeography, 2025)
Aim Habitat‐forming species play a critical role in coral reef ecosystems by creating complex physical structures for marine species. Driven by climate change, these habitat‐forming species are undergoing considerable shifts in their geographical distribution, which might trigger cascading effects via protection mutualisms, leading to alterations in the relationships between species. We examined the role of habitat‐forming species in regulating spatial distributions of their mutualistic protectors' influence. Location Global coastal ocean. Methods We used species distribution models to examine how suitable habitats for organisms that form mutualistic relationships with habitat‐forming species respond to climate change, focusing on two representative macrosymbiotic relationships in coral reefs: Coral–coral crab and sea anemone–clownfish. Results The results revealed that corals are more sensitive to climate change than sea anemones, experiencing greater range contractions under projected future conditions. Consequently, the distribution ranges of both coral‐mutualistic crabs and sea anemone‐mutualistic clownfishes are expected to reduce even further when protection mutualisms are considered. Coral crabs are projected to undergo a more rapid range size loss than clownfishes. Main Conclusion These findings highlight the importance of incorporating interspecific interactions among habitat‐forming species into predictions of potential shifts in the biogeographic distributions of mutualistic protectors under climate change.

Synergistic effects of air pollutants and CO2 at Chinese thermal power plants based on real-monitored data - Ling Tang; Shuangyue Qian; Ruxing Wan; Song Lv; Jieyi Li; Jiaxin Zhang; Wei Shuai; Shuo Qi; Peng Wang; Jiabao Qu; Yinghao Chu (Journal of Environmental Management, 2025)

Flower-Like bismuth hydroxide/nitrogen-doped carbon nanotube catalyst-FerrateVI System: Selective generation of BismuthV and rapid oxidation of organic pollutants - Mingzhu Liu; Xiaoyu Li; Yumeng Qi; Nannan Wu; Zhongbo Wei; Kai Tang; Virender K. Sharma; Ruijuan Qu (Chemical Engineering Journal, 2025)

A sensitive humidity-responsive actuator based on dispersing graphene oxide into chitosan- sodium alginate nanofibers - Yonghao Chen; Meijie Qu; Chenshen Liu; Shuhui Li; Xincheng Wang; Daixuan Gong; Ping Tang; Yuezhen Bin (Chemical Engineering Journal, 2025)

Aluminum-based solar interfacial evaporator prepared by picosecond laser processing combined with fire treatment used for high-efficiency water-electric cogeneration - Dongkai Chu; Zhiliang Tang; Shuangshuang Hu; Fangyu Yang; Shuoshuo Qu; Weishun Mao; Peng Yao (Chemical Engineering Journal, 2025)

Diffusion-driven multi-modality medical image fusion - Jiantao Qu; Dongjin Huang; Yongsheng Shi; Jinhua Liu; Wen Tang (Medical & Biological Engineering & Computing, 2025)

Stepwise leaching rare earth from weathered crust elution-deposited rare earth ores by the inhibition leaching of aluminum with HMTA - Zhengyan He; Qin Zuo; Yuchen Tang; Wenqian Cui; Zhigao Xu; Ming Wu; Jun Qu; Ruan Chi (Environmental Science and Pollution Research, 2025)

Heavy metal contamination in fish and human health risks from lakes of a mega inter-basin water diversion - Wenxia Fan; Wentong Xia; Lian-Shin Lin; Han Liu; Xiao Qu; Wei Xin; Lizhou Tang; Yushun Chen (Chemosphere, 2025)

GAIN: A long-term maize germplasm innovation plan - Yang Wang; Peng Zhang; Yingjie Xiao; Hai-Jun Liu; Junqiang Ding; Yanzhi Qu; Jionghao Gao; Wenlong Li; Xiangyang Guo; Angui Wang; Wenqiang Li; Gengshen Chen; et al. (Molecular Plant, 2025)

Novel role of Silver(I) as electron shuttle for polymerization of chlorophenols by permanganate oxidation - Boying Liu; Zhiwei Liu; Shengnan Zhang; Xiaosheng Tang; Zunyao Wang; Ruijuan Qu (Journal of Hazardous Materials, 2025)

Promotional activity of an uncharacterized protein Bm0979 on Nosema bombycis in silkworm, bombyx mori - Yujia Fang; Qiong Yu; Wenzhe Chen; Zhenghao Han; Qingsheng Qu; Zhenwei Jia; Shidong Jiang; Jie Cheng; Xudong Tang; Ping Qian (Journal of Asia-Pacific Entomology, 2025)

Monitoring the interannual dynamic changes of soil organic matter using long-term Landsat images - Chang Liu; Qian Sun; Chi Zhang; Wentao Chen; Xuzhou Qu; Boyi Tang; Kai Ma; Xiaohe Gu (Precision Agriculture, 2025)

Methods and challenges in computer vision-based livestock anomaly detection, a systematic review - Yutong Deng; Hongchun Qu; Ansong Leng; Xiaoming Tang; Shidong Zhai (Biosystems Engineering, 2025)

Gender-specific effects of prenatal polystyrene nanoparticle exposure on offspring lung development - Wenxia Bu; Mengjiao Yu; Xinyi Ma; Zhaoping Shen; Jialing Ruan; Yi Qu; Ruiyao Huang; Peng Xue; Yuanyuan Ma; Juan Tang; Xinyuan Zhao (Toxicology Letters, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Trends and magnitude of urban-rural food GHG inequalities over 33 years (1990–2022): Drivers, disparities, and future trends - Dai Wang; Jiansheng Qu; Tek Narayan Maraseni; Jinyu Han; Hengji Li; Li Xu; Jixing Tang; Dingye Wu (Journal of Cleaner Production, 2025)

Co-application of microalgae and biochar increases yield and mitigates greenhouse gas emissions in saline-alkali soil - Chao Ma; Zhe Xu; Wei Yang; Tao Tang; Qi Liu; Dongliang Zhang; Prashanth Prasanna; Zhongyi Qu (Field Crops Research, 2025)

Citrus fruit diameter estimation in the field using monocular camera - Hongchun Qu; Haitong Du; Xiaoming Tang; Shidong Zhai (Biosystems Engineering, 2025)

An improved adaptive large neighborhood search algorithm to solve a bi-level medical waste location-routing problem with infection control - Chu Tang; Qu Wei; Dongqing Zhang; Jinan Sun; Guido Perboli; Zhaoxia Guo; Kang Li (Waste Management, 2025)

Depositional systems constraining the distribution of hydrothermal dolostone geobodies: A case study of Permian Guadalupian dolostone in the eastern Sichuan Basin - Lu Shi; Ziye Lu; Fei Li; Hairuo Qing; Wenzhuo Jiang; Wei Li; Zenghua Li; Ning Ye; Bei Zhu; Qi Tang; Haizhou Qu; Yang Xiao; et al. (Sedimentary Geology, 2025)

Quorum sensing-enhanced electron transfer in anammox consortia: A mechanism for improved resistance to variable-valence heavy metals - Caiyan Qu; Jiong Tang; Jingyu Liu; Wenming Wang; Fengming Song; Siyuan Cheng; Xi Tang; Chong-Jian Tang (Journal of Hazardous Materials, 2025)

Phototransformation behavior of octachlorodibenzofuran (OCDF) on the surface of river suspended particulate matter: Kinetics and products formation mechanism - Junyan Wei; Mengqiang He; Jianqiao Xu; Zhongbo Wei; Xiaosheng Tang; Qing Zheng; Zunyao Wang; Ruijuan Qu (Environmental Pollution, 2025)

Towards digitalized maintenance of operating tunnels: A text documents-based defect evaluation and visualization - Xuefeng Ou; Cong Tang; Tongming Qu; Shiquan Xu; Ye Zhou; Jiao Tian (Tunnelling and Underground Space Technology, 2025)

Characterization of microbial communities in Douchi and their role in vitamin K2 production - Guoliang Tang; Baolong Li; Wenwen Qu; Junbin Ye; Xiaobing Liu; Xuesong Xiang; Yongye Sun (Food Bioscience, 2025)

Aluminum promotes B1 cells to produce IL-10 and impairs adaptive immune system - Ting Liu; Wei Wang; Jun Du; Hongyue Liu; Jiaojiao Wu; Chuanxuan Wang; MengKe Tang; Yalin Liu; Yingzi Ju; Weidong Qu; Jianheng Zheng; Yifan Zhao; et al. (Environmental Pollution, 2025)

Intumescent flame retardant behavior of aryl Schiff base triazine piperazine char-forming agent with heat-induced cyclization self-crosslinking trait in polypropylene - Shuwei Liu; Yong Qiu; Tiantian Wang; Dejin Li; Lijun Qian; Wang Xi; Jingyu Wang; Lijie Qu; Wei Tang (Chemical Engineering Journal, 2025)

Amino-tuned S-scheme ZIF nano-heterojunction coating up/downconversion nanoparticles for near-infrared-triggered catalytic therapy and bioimaging - Chunsheng Li; Jiawei Qu; Yunlong Li; Shuang Liu; Zhengyang Tang; Qiang Wang; Jin Ye; Jiating Xu; Na Niu; Ligang Chen; Piaoping Yang (Chemical Engineering Journal, 2025)

Co-carrier effect of polyethylene microplastics in the heterogenous phototransformation of o,p’-DDT in suspended particulate matter-Yangtze River water system - Junyan Wei; Jianqiao Xu; Xinyuan Wei; Dongmei Zhou; Zhongbo Wei; Xiaosheng Tang; Qing Zheng; Zunyao Wang; Ruijuan Qu (Chemical Engineering Journal, 2025)

Review on synthesis of lactic acid and lactates from biomass derived carbohydrates via chemocatalysis routes - Ruite Lai; Fei Qu; Meiting Ju; Chao Xie; Hengli Qian; Tianliang Xia; Chengxu Wang; Guanjie Yu; Yao Tang; Xinyu Bai; Qidong Hou (Bioresource Technology, 2025)

Potential of hyperspectral LiDAR in individual tree segmentation: A comparative study with multispectral LiDAR - Ao Wang; Shuo Shi; Jian Yang; Bowei Zhou; Yi Luo; Xingtao Tang; Jie Du; Sifu Bi; Fangfang Qu; Chengyu Gong; Wei Gong (Urban Forestry & Urban Greening, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Phosphorus speciation in the hyporheic zone and its response to sediment-water quality-biological activity coupling effect - Yue Qu; Jinxi Song; Yongqing Long; Nan Li; Songzhe Fu; Bin Tang; Qihao Tao; Qifan Cui; Ken Qin (Journal of Environmental Management, 2025)

Engineering noble metal-free nickel catalysts for highly efficient liquid fuel production from waste polyolefins under mild conditions - Xinlei Han; Jiuxuan Zhang; Zhengyan Qu; Tuo Ji; Feng Zeng; Hong Jiang; Jun Huang; Zhenchen Tang; Weihong Xing; Rizhi Chen (Fuel, 2025)

LINC01224 promotes the Warburg effect in gastric cancer by activating the miR-486-5p/PI3K axis - Yuling Bin; Minji Liu; Rong He; Pingfei Tang; Weiming Qu; Dajun Wu; Lin Tan; Qian Wang; Peng Jiang; Hongsai Hu (In Vitro Cellular & Developmental Biology - Animal, 2025)

Amidine-functionalized aggregation-induced emission luminogen and a 3D-printed digital sensor platform for ultrafast and visual detection of heparin - Feilong Tang; Siyu Shi; Chiyuan Wei; Yuanqiang Sun; Ran Yang; Lingbo Qu; Zhaohui Li (Analytica Chimica Acta, 2025)

Evidence of sewage discharge on the coalescence mechanism of aquatic microbial communities during high amplitude hydrological periods - Xin Kou; Shier Huang; Rui Bian; Qingwen Tang; Hui Wang; Song Liu; Li Wang; Weixiao Qi; Xiaofeng Cao; Huachun Lan; Huijuan Liu; Jiuhui Qu (Science of The Total Environment, 2025)

Aluminum-based solar seawater desalination interface evaporator processed by picosecond laser combined with fire treatment - Zhiliang Tang; Shuangshuang Hu; Dongkai Chu; Shuoshuo Qu; Yuying Yang; Peng Yao (Desalination, 2025)

Micron-level aggregate initiated ultra hydrophobicity with enhanced intumescent flame retardancy, smoke suppression, and toughness simultaneously in polypropylene - Shanzhe Li; Wei Tang; Lijun Qian; Junxiao Li; Lijie Qu; Jingyu Wang; Wang Xi; Yong Qiu (Chemical Engineering Journal, 2025)

Elevated pCO2 may increase the edible safety risk of clams exposed to toxic Alexandrium spp. - Min Pang; Yuchen Gong; Hongju Chen; Ying Shi; Zhao Li; Xiuping He; Junhui Chen; Xuexi Tang; Zongling Wang; Xuelei Zhang; Pei Qu (Science of The Total Environment, 2024)

Effect of steady boundary-layer flow on the hydrodynamic forces on a near-wall cylinder in currents - Yunfei Teng; Terry Griffiths; Liang Cheng; Yan Qu; Hongwei An; Scott Draper; Zhe Gao; Guoqiang Tang; Lin Lu (Ocean Engineering, 2024)

Design and multi parameter performance optimization of the bionic robotic fish driven by tail fin - Wei Tang; Zhenping Yu; Yunfei Wang; Peizheng Chen; Houde Liu; Xueqian Wang; Xiaohao Wang; Juntian Qu (Ocean Engineering, 2024)

Formation analysis and hazard assessment of the landslide-debris flow disaster chain in small watersheds of the reservoir type - Jingkai Qu; Weimin Yang; Yiguo Xue; Chunshan Zhang; Fanmeng Kong; Jiajia Li; Feipeng Wan; Siqi Ma; Haibing Tang; Chuancheng Xu (Bulletin of Engineering Geology and the Environment, 2024)

Impact of Ultra-Low Emission Technology of Thermal Power Plants on Air Quality in China - Wenda Zhu; Nan Li; Jiandong Li; Senhu Qu; Keqin Tang; Yang Xu; Fengyi Chang (Aerosol Science and Engineering, 2024)

The causal link between nitrogen structure and physiological processes of Ulva prolifera as the causative species of green tides - Baixue Sun; Xinyu Zhao; Tongfei Qu; Yi Zhong; Chen Guan; Chengzong Hou; Liuqing Tang; Xuexi Tang; Ying Wang (Science of The Total Environment, 2024)

A novel reservoir dispatching rules extraction framework based on hybrid embedding informer - Shuai Liu; Hui Qin; Zhengyang Tang; Keyan Shen; Xu Yang; Zhiwei Zheng; Yuhua Qu; Zhiwei Jia (Journal of Hydrology, 2024)

Spontaneous imbibition in hydrate-bearing sediments under creep - Kailun Wang; Gang Lei; Jiangtao Qu; Yang Wu; Wan Cheng; Jiadi Tang; Yuyi Lu (Gas Science and Engineering, 2024)

The joint impact of PM2.5 constituents on the risk of cerebrovascular diseases hospitalization: A large community-based cohort study - Shirui Chen; Yuqin Zhang; Ziqiang Lin; Ruqing Liu; Lingling Zheng; Xiuyuan Chen; Shao Lin; Yanji Qu; Chun Hao; Hui Tang; Jing Wei; Wangjian Zhang; et al. (Environmental Research, 2024)

Noble metal-free tandem catalysis enables efficient upcycling plastic waste into liquid fuel components - Jie Sun; Changdong Wu; Yuchen Zhou; Jiuxuan Zhang; Zhengyan Qu; Feng Zeng; Zhenchen Tang; Weihong Xing; Rizhi Chen (Chemical Engineering Journal, 2024)

Improving carrier transport for stable and efficient perovskite solar cells via MXene-modified 2D perovskite capping layer - Yaobin Li; Yu Zou; Shuang Yang; Hantao Wang; Wenjin Yu; Haoqing Guo; Xiangdong Li; Yunxuan Cao; Yueli Liu; Zhenyu Tang; Bo Qu; Lixin Xiao; et al. (Chemical Engineering Journal, 2024)

Patterned Laser-Induced graphene enabling a High-Performance gas sensing Split-Ring resonator - Kishor Kumar Adhikari; Luqman Ali; Jie Wei; Yang Yi; Xiaocong Tang; Zheyi Li; Ju Gao; Liangzhong Mei; Yishun Qu; Junli Yin; Cong Wang (Chemical Engineering Journal, 2024)

Sensitive detection of persulfate by a novel self-powered electrochemical sensor with carbon cloth electrodes modified with tin-doped cobalt tetroxide - Wanting Tang; Weifeng Liu; Zhe Li; Ke Liu; Tao Jiang; Shanhui Wang; Kai Qu; Jiayi Li; Xingzhu Zhang; Yimin Zhu (Environmental Science and Pollution Research, 2024)

Spatial heterogeneity of soil potassium geochemistry: A case study from Tianfu New Area, Chengdu, China - Fan Meng; Yang Wu; Liang Tang; Fang Yang; Lingfei Qu; Yang Li (Ore and Energy Resource Geology, 2024)

Spatial distribution of mine areas in the Luanhe River Basin, China: Clustering implications - Jingjing Li; Liang Tang; Jinsong Yang; Lingfei Qu; Fan Meng; Feng Jiang; Lei Xu; Sijie He (Ore and Energy Resource Geology, 2024)

Low-frequency ultrasound assisted contact-electro-catalysis for efficient inactivation of Microcystis aeruginosa - Peiyun Wei; Mengxia Tang; Yao Wang; Baowei Hu; Xiaolei Qu; Yanfeng Wang; Guandao Gao (Journal of Hazardous Materials, 2024)

Identification of microbiological genomes carrying antibiotic resistance genes and virulence factor genes for microbiological risk assessment in filter backwash water - Yongjie Huang; Xiaoyao Weng; Xinlu Qu; Tianxiao Sun; Weiwei Zhang; Shumin Yang; Xin He; Yuan Xiao; Tianyang Zhang; Yulin Tang (Journal of Environmental Chemical Engineering, 2024)

Highly acid-stable polyvinyl alcohol/chitosan/phytic acid aerogel for selective separation of uranium from actual wastewater - Xiaoyan Wu; Qiuyang Tang; Xiaowen Zhang; Qi Fang; Yilong Hua; Tao Cai; Wei Tan; Jie Kou; Ziyin Wang; Mengge Tian; Jiayi Qu; Mi Li (Journal of Environmental Chemical Engineering, 2024)

Effects of Aeromonas infection on the immune system, physical barriers and microflora structure in the intestine of juvenile grass carp (Ctenopharyngodon idella) - Meixing Guo; Ran Peng; Kelan Jin; Xia Zhang; Huilan Mo; Xiang Li; Fufa Qu; Jianzhou Tang; Shenping Cao; Yonghua Zhou; Zhimin He; Zhuangwen Mao; et al. (Fish & Shellfish Immunology, 2024)

A carboxymethyl cellulose/chitosan-based hydrogel harvests robust adhesive, on-demand detachment and self-healing performances for deep burn healing - Mengya Li; Haofan Qu; Qin Li; Shengchang Lu; Yang Wu; Zuwu Tang; Xiaolong Liu; Zhanhui Yuan; Liulian Huang; Lihui Chen; Hui Wu (Chemical Engineering Journal, 2024)

Precise fine-tuning of the defect degree in FeNi-TDC nanoarrays via fluorinated acetic acid for rapid urea-assisted hydrogen production in seawater - Qianqian Wang; Xiaoyan Ma; Fengjin Qu; Ran bi; Senyang Song; Pengcheng Ma; Jing Sun; Fang Chen; Qiufan Tang (Chemical Engineering Journal, 2024)

In-situ polymerization of dual monomers for constructing a highly elastic PAA-co-PAM network enables efficient and stable Carbon-based perovskite solar cells - Hongbing Ran; Qiyu Qu; Shiyu Wang; Yue Zhao; Yulin Wang; Xiangjie Chen; Yiwen Tang (Chemical Engineering Journal, 2024)

Disease Modules Associated with Unfavorable Sleep Patterns and Their Genetic Determinants: A Prospective Cohort Study of the UK Biobank - Huazhen Yang; Can Hou; Wenwen Chen; Yu Zeng; Yuanyuan Qu; Yajing Sun; Yao Hu; Xiangdong Tang; Huan Song (Phenomics, 2024)

Knowledge Graph-Driven Weather Overview Generation for the Beijing 2022 Winter Olympic Games - Hanhua Qu; Jiangping Zheng; Wei Tang; Muhua Wang; Tianyue Wang (Journal of Meteorological Research, 2024)

New insights into the controversy of reactive mineral-controlled arsenopyrite dissolution and arsenic release - Haojie Qu; Kengbo Ding; Ming Ao; Zekai Ye; Taicong Liu; Zunhe Hu; Yingjie Cao; Jean-Louis Morel; Alan J M Baker; Yetao Tang; Rongliang Qiu; Shizhong Wang (Water Research, 2024)

A model reduction framework of flow maldistribution and mitigation strategy for parallel flow field based polymer exchange membrane fuel cell - Ning Wang; Zetian Tang; Zhiguo Qu; Yun Wang (Journal of Cleaner Production, 2024)

Developing environmental sustainability policy – How financing and subsidies are influencing green innovation in mineral extraction industries in China - Helen Huifen Cai; Naqib Ullah Khan; Shirley Tang; Mujahid Siddiqui; Mengyao Xia; Hongyan Qu (Journal of Environmental Management, 2024)

Evaluating carbon emissions reduction compliance based on 'dual control' policies of energy consumption and carbon emissions in China - Wen Wen; Yang Su; Ying-er Tang; Xingman Zhang; Yuchen Hu; Yawen Ben; Shen Qu (Journal of Environmental Management, 2024)

Assessing the causal relationship between immune cells and prostatitis: evidence from bidirectional mendelian randomization analysis - Genyi Qu; Weimin Jiang; Zhaohui Long; Xing Zhou; Yijie Wang; Guang Yang; Cheng Tang; Yong Xu (Mammalian Genome, 2024)

Corrigendum to “Unveiling the role of pore characteristics in sludge dewatering: Visualization by Nano-CT and micromodel study” [Water Research 252 (2024) 12191] - Yue Wang; Jiawei Li; Fan Feng; Caiyan Qu; Chongjian Tang; Qingwei Wang; Wenchao Zhang; Xu Yan; Zhang Lin (Water Research, 2024)

Determining toxicity of europium oxide nanoparticles in immune cell components and hematopoiesis in dominant organs in mice: Role of lysosomal fluid interaction - Min Li; Jie Gao; Linlin Yao; Liu Zhang; Danyang Li; Zikang Li; Qi Wu; Shunhao Wang; Jie Ding; Yaquan Liu; Minghao Wang; Gang Tang; et al. (Science of The Total Environment, 2024)

Baseline of susceptibility, risk assessment, biochemical mechanism, and fitness cost of resistance to dimpropyridaz, a novel pyridazine pyrazolecarboxamide insecticide, in Bemisia tabaci from China - Juan Tang; Cheng Qu; Qianyuan Zhan; Daofeng Zhang; Jinda Wang; Chen Luo; Ran Wang (Pesticide Biochemistry and Physiology, 2024)

A peptide from yak ameliorates hypoxia-induced kidney injury by inhibiting inflammation and apoptosis via Nrf2 pathway - Feiyan Yang; Zhongxing Chu; Qi Wu; Guangfan Qu; Zeyu He; Jun An; Yiping Tang; Shuguo Sun; Dun Ci; Feijun Luo (Food Bioscience, 2024)

Developing defined starter culture for reproducible profile of flavour compound in Chinese xiaoqu baijiu fermentation - Yifu Zheng; Guanyi Qu; Qiang Yang; Shenxi Chen; Jie Tang; Shengzhi Yang; Qun Wu; Yan Xu (Food Microbiology, 2024)

Fish decay-accelerating factor (DAF) regulates intestinal complement pathway and immune response to bacterial challenge - Xia Zhang; Yuhan Zhang; Ting Wu; Hao He; Ran Peng; Kelan Jin; Huilan Mo; Fufa Qu; Jianzhou Tang; Yonghua Zhou; Yalin Yang; Zhigang Zhou; et al. (Fish & Shellfish Immunology, 2024)

Erythrocyte membrane-camouflaged nanodelivery strategy enhances gene editing efficiency of Cas9 RNP for boosting tumor senescence - Silin Shi; Chao Chen; Xueting Shen; Shiyu Du; Kunguo Liu; Yamei Gao; Lihua Qu; Jingjing Yang; Mengfan Tang; Xin Han (Chemical Engineering Journal, 2024)

Polygonum ciliinerve (Nakai) Ohwi: a review of its botany, traditional uses, phytochemistry, pharmacology, pharmacokinetics and toxicology - Qiong Qu; Ying Zhang; Xiaomei Zhao; Xinbo Zhang; Xuan Wei; Yingying Tang; Xuan Lei; Xiao Song (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Degradation of hydroxypropyl guar gum by dual oxidant system catalyzed by hydrotalcite supported zero-valent transition metal - B. Bai; Q. Liu; T. Li; R. Zhou; C. Qu; Y. Tang (International Journal of Environmental Science and Technology, 2024)

Chronic Fluoride Exposure Induces Ovarian Dysfunction and Potential Association with Premature Ovarian Failure in Female Rats - Xiaoke Tang; Hongjuan Li; Yali Wang; Li Zeng; Ling Long; Yajun Qu; Hui Yang; Xiaolin Zhang; Yanmin Li; Yanni Yu; Qi Zhou; Man Luo (Biological Trace Element Research, 2024)

An application of hierarchical MgAl hydrotalcite in the highly efficient treatment of oilfield macromolecular contaminants - Chenye Yang; Qi Liu; Tao Li; Rui Zhou; Chengtun Qu; Ying Tang (Environmental Science and Pollution Research, 2024)

Bioaccessibility and human health risks of arsenic from geological origin in lateritic red soil on construction land - Lu-Yao Ding; Guang-Yong Tang; Ming-Zhu Chen; Fo-Peng Wang; Jun-Feng Wang; Han-Jie Ye; Qu-Sheng Li (Chemosphere, 2024)

Overcoming research challenges: In vitro cultivation of Ameson portunus (Phylum Microsporidia) - Ming Fu; Hongnan Qu; Yongliang Wang; Jingyu Guan; Tian Xia; Kai Zheng; Liyuan Tang; Chunxue Zhou; Huaiyu Zhou; Wei Cong; Jinyong Zhang; Bing Han (Journal of Invertebrate Pathology, 2024)

Knockdown of one cytochrome P450 gene CYP6DW4 increases the susceptibility of Bemisia tabaci to dimpropyridaz, a novel pyridazine pyrazolecarboxamide insecticide - Juan Tang; Qinghe Zhang; Cheng Qu; Qi Su; Chen Luo; Ran Wang (Pesticide Biochemistry and Physiology, 2024)

Association between air pollution and male sexual function: A nationwide observational study in China - Ziyuan Shen; Feng Zhang; Zihan Guo; Rui Qu; Yiqiu Wei; Jingxuan Wang; Weiqian Zhang; Xing Xing; Yan Zhang; Jue Liu; Dongdong Tang (Journal of Hazardous Materials, 2024)

Research progress of microfluidics-based food safety detection - Wenjun Jiang; Qu Tang; Yidan Zhu; Xijuan Gu; Li Wu; Yuling Qin (Food Chemistry, 2024)

Dynamic transport characteristics and performance response of commercial-size polymer electrolyte membrane fuel cell stack: An experimental study - Xuhui Wen; Ning Wang; Xianji Huang; Qiyao Wang; Zetian Tang; Zhiguo Qu; Guangyou Xie (Chemical Engineering Journal, 2024)

Multifunctional CeO2 nanozymes for mitigating high-glucose induced senescence and enhancing bone regeneration in type 2 diabetes mellitus - Zhuoran Wang; Yilin Zhang; Sishi Chen; Yang Qu; Mengchen Tang; Wenying Wang; Weichang Li; Lisha Gu (Chemical Engineering Journal, 2024)

Correction to: A 5-and a-half-year-experiment shows precipitation thresholds in litter decomposition and nutrient dynamics in arid and semi-arid regions - Hao Qu; Eduardo Medina-Roldán; Shaokun Wang; Xujun Ma; Xinyuan Wang; Xia Tang; Liangxu Liu (Biology and Fertility of Soils, 2024)

A review of quorum sensing regulating heavy metal resistance in anammox process: Relations, mechanisms and prospects - Caiyan Qu; Fan Feng; Jia Tang; Xi Tang; Di Wu; Ruiyang Xiao; Xiaobo Min; Chong-Jian Tang (Critical Reviews in Environmental Science and Technology, 2024)

Unveiling the role of pore characteristics in sludge dewatering: Visualization by Nano-CT and micromodel study - Yue Wang; Jiawei Li; Fan Feng; Caiyan Qu; Chongjian Tang; Qingwei Wang; Wenchao Zhang; Xu Yan; Zhang Lin (Water Research, 2024)

Exploration of natural processes and anthropogenic inputs by Zn isotopes in suspended particulate matter: A case study from the Lancang River in Southwest China - Yang Tang; Guilin Han; Rui Qu; Jinke Liu; Man Liu (Environmental Pollution, 2024)

pH-temperature coupled regulation for promoted nanofluidic osmotic energy conversion - Xu Zhang; Zhiguo Qu; Zetian Tang; Mazhar Iqbal (Desalination, 2024)

Enhanced Removal of Sulfonated Lignite from Oilfield Wastewater by Soft Colloidal Templated Porous Structure of MgAl-LDH - Ying Tang; Bingbing Bai; Ya Wu; Bo Yang; Ling Zhou; Chentun Qu (Water, Air, & Soil Pollution, 2024)

Effect of different defects on the competitive adsorption of formaldehyde and water on the surface of carbon materials: Density functional theory study - Zhonghua Wang; Zekun Sun; Haiqian Zhao; Jun Li; Xing Zhang; Jiuyang Jia; Kaibo An; Ziyu Tang; Mingqi He; Zhibin Qu (Science of The Total Environment, 2024)

Chuaria and Tawuia fossils from ∼1.0 Ga rocks in North China: Implications for a polyphyletic origin of Chuaria and a potential biological link between these two widespread Proterozoic taxa - Changtai Niu; Guangjin Li; Qing Tang; Xiaopeng Wang; Rui Huang; Hanzhi Qu; Mingyang Qiu; Bin Wan; Zhe Chen; Chuanming Zhou; Ke Pang; Xunlai Yuan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

A Highly Efficient and Energy Saving Electrochromic Platform for Adaptive Visible and Near-Infrared Light Modulation - Dajiang Tang; Junxin Wang; Xiaoyu Huang; Dashui Zhang; Sheng Cao; Linfei Yin; Zhangfa Tong; Hongbing Ji; Rachel C. Evans; Hui-Ying Qu (Chemical Engineering Journal, 2024)

Exploiting the synergistic antibacterial activity of shikimic acid and ceftiofur against methicillin-resistant Staphylococcus aureus - Zhuohui Zhang; Qianqian Xu; Yan Wang; Shiyin Qu; Junjie Tan; Yulong Tang; Pishun Li; Xiaofeng Zheng (World Journal of Microbiology and Biotechnology, 2024)

A 5-and a-half-year-experiment shows precipitation thresholds in litter decomposition and nutrient dynamics in arid and semi-arid regions - Hao Qu; Eduardo Medina-Roldán; Shaokun Wang; Xujun Ma; Xinyuan Wang; Xia Tang; Liangxu Liu (Biology and Fertility of Soils, 2024)

Effects of Different Protein Sources on Growth Performance, Muscle Flavor Substances and Quality Structure in Triploid Crucian Carp - Liquan Yang; Chenglin Yi; Yujian Mo; Zhimin He; Zhehua Xu; Yimiao He; Yongkang Ouyang; Zhuangwen Mao; Fufa Qu; Jianzhou Tang; Zhen Liu; Zhijia Fang; et al. (Fishes, 2024)
A 56-day feeding trial was conducted to evaluate the effect of different dietary protein sources on the growth performance, muscle flavor substances, and quality structure of Triploid Crucian Carp. Three isonitrogenous (32.00%), isolipidic (8.00%), and isoenergetic (18.00 MJ kg−1) practical diets were formulated. These diets consisted of fishmeal as the animal-derived protein source (AP), a combination of soybean meal and rapeseed meal as the plant-derived protein source (PP), and a mixture of fishmeal, soybean meal, and rapeseed meal as the mixed protein source (MP). Each diet was randomly assigned to triplicate tanks of fish and each tank was stocked with 25 fish (11.5 ± 0.4 g). The fish were fed until apparent satiation twice a day. The results showed a significant enhancement in the growth performance of Triploid Crucian Carp in the AP group compared with both the MP and PP groups (p

Accelerating the environmental applications of black phosphorus: A review - Jiachen Yu; Haijiang Tian; Gengchang Lai; Jiahong Wang; Jing Zhao; Gang Tang; Jie Gao; Xue-Feng Yu; Guangbo Qu; Haiyan Zhang; Guibin Jiang (Science of The Total Environment, 2024)

Enhanced peroxymonosulfate activation via heteroatomic doping defects of pyridinic and pyrrolic N in 2D N‑doped carbon nanosheets for BPA degradation - Guojuan Qu; Peng Jia; Shuai Tang; Md. Nahid Pervez; Yixiong Pang; Bin Li; Chengjin Cao; Yaping Zhao (Journal of Hazardous Materials, 2024)

InN@In2S3 Core-Shell nanorod for oxygen-free and penetration depth-unrestricted photodynamic therapy against glioblastoma - Boyang Liu; Yufei Lan; Tao Yang; Xin Tang; Chao Zhang; Boming Zuo; Xiaodie Li; Qu Yue; Zhao Wang; Xiangyang Zhong; Xin Luo; Tianci Zeng; et al. (Chemical Engineering Journal, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

A comparative study of air pollution tolerance capabilities of four tree species in Xi’an city, China - J. Zheng; X. Qu; R. Hou; X. Tang; Z. Xu; Z. Huang; Z. Wang; W. Zhang; C. Yang; T. Li (International Journal of Environmental Science and Technology, 2024)

Oxidation of 4-tert-butylphenol by potassium permanganate and reduced formation of disinfection byproducts from chlorination - Yeping Liang; Mingzhu Liu; Chenxi Sun; Xiaosheng Tang; Ahmed A. Allam; Jamaan S. Ajarem; Saleh Maodaa; Zunyao Wang; Ruijuan Qu (Journal of Environmental Chemical Engineering, 2023)

Fluviispira vulneris sp. nov., isolated from human wound secretions - Peijuan Tang; Na Peng; Pengwen Ouyang; Sheng Long; Zhenhua Wei; Xingchun Chen; Pinghua Qu; Liangyi Xie (Antonie van Leeuwenhoek, 2023)
Human infections by environmental bacteria is becoming an increasing problem and has become a matter of great concern due to the adverse effects worldwide. In this study, we reported a new environmental pathogen. Isolate GX5518 T was a novel Gram-negative, aerobic, non-motile, pleomorphic and red-pigmented bacterium, was isolated from human wound secretions (GuangXi, People’s Republic of China). Growth occurred at pH 6.0–8.0 (optimum, pH 7.0) and 10–37 °C (optimum, 28–32 °C) with 0–1.5% (w/v) NaCl in R2A agar. Comparative analysis of the 16S rRNA gene sequences revealed that isolate GX5518 T was closely related to Fluviispira sanaruensis JCM 31447 T (99.73%) and Fluviispira multicolorata 33A1-SZDP T (98.49%). However, the estimated ANI values of the isolate GX5518 T compared to the F. sanaruensis JCM 31447 T and F. multicolorata 33A1-SZDP T were 88.67% and 77.35%, respectively. The estimated dDDH, ANI and AAI values between isolate GX5518 T and its closely related strains were below the threshold values generally considered for recognizing a new species. The genome size was 3.6 Mbp and the DNA G + C content was 33.1%. The predominant fatty acids (> 5%) in GX5518 T cells were iso-C 15:0 , C 16:0 , C 17:0 , C 17:1 ω 8 c and C 16:1 ω 7 c /C 16:1 ω 6 c . The major menaquinone was MK-8 (86.9%). The polar lipids were phosphatidylethanolamine (PE), phosphatidylglycerol (PG) and three unknown lipids (L1-3). The chemical composition was different from that of the F. sanaruensis JCM 31447 T . Comparative genomics analysis between isolate GX5518 T and its related strains revealed that there were a number of genes involved in resistance to antibiotics and toxic compounds in isolate GX5518 T , which were responsible for the copper homeostasis, cobalt-zinc-cadmium resistance, resistance to fluoroquinolones, and zinc resistance. Based on the phenotypic, chemotaxonomic, and genomic analyses, isolate GX5518 T (= CGMCC 1.18685 T = KCTC 82149 T ) represents a novel species of the genus Fluviispira , for which the name Fluviispira vulneris sp. nov. is proposed.

Potentiality of ultraspectral sensor in biophysical and biochemical vegetation parameter inversion - Shuo Shi; Zixi Shi; Zhongqiu Sun; Wei Gong; Lu Xu; Bowen Chen; Fangfang Qu; Xingtao Tang (International Journal of Remote Sensing, 2023)

Synthesis and demulsification mechanism of an ionic liquid with four hydrophobic branches and four ionic centers - Qian Qu; Huan Li; Shuman Li; Zhijie Hu; Mingzhao Zhu; Junhong Chen; Xuebiao Sun; Yuqi Tang; Zejun Zhang; Yuanzhu Mi; Weichu Yu (Chemosphere, 2023)

Bioenergy production from swine wastewater based on a combined process of anaerobic dynamic membrane reactor and microalgae cultivation: Feasibility and performance - Jialing Tang; Hao Yang; Yunhui Pu; Yisong Hu; Xiangjiang Qu; Si Chen; Xiaochang C. Wang; Huu Hao Ngo; Yuyou Li; Abdelfatah Abomohra (Science of The Total Environment, 2023)

Contribution of the bacterial community of poorly fermented oat silage to biogas emissions on the Qinghai Tibetan Plateau - Chaosheng Liao; Binbin Na; Xiaolong Tang; Man Zhao; Changbing Zhang; Shiyong Chen; Minghong You; Binqiang Bai; Lizhuang Hao; Dorjeeh Tondrob; Guangpeng Qu; Shuqing Yang; et al. (Science of The Total Environment, 2023)

Reliability analysis of floating offshore wind turbine generator based on failure prediction and preventive maintenance - Chuanyang Zhao; Hongbing Liu; Xianqiang Qu; Mingxuan Liu; Ruitong Tang; Ankui Xie (Ocean Engineering, 2023)

Lithium impacts the function of hematopoietic stem cells via disturbing the endoplasmic reticulum stress and Hsp90 signaling - Yalin Liu; Yifan Zhao; Jiaojiao Wu; Ting Liu; MengKe Tang; Ye Yao; Peng Xue; Miao He; Yanyi Xu; Peng Zhang; Minghua Gu; Weidong Qu; et al. (Food and Chemical Toxicology, 2023)

Mercury chloride activates the IFNγ-IRF1 signaling in myeloid progenitors and promotes monopoiesis in mice - Mengke Tang; Yifan Zhao; Yue Zhai; Yufan Zhang; Yalin Liu; Ting Liu; Jiaojiao Wu; Leyi He; Ye Yao; Peng Xue; Miao He; Yanyi Xu; et al. (Environmental Pollution, 2023)

Molten salt-assisted anti-defect engineering to tailor ordered, highly crystalline g-C3N4 nanorods for efficient photocatalytic H2O2 production - Tingyu Yang; Yanqi Tang; Fengyi Yang; Jiafu Qu; Xiaogang Yang; Yahui Cai; Feng Du; Chang Ming Li; Jundie Hu (Chemical Engineering Journal, 2023)

Synergistic activation of peroxymonosulfate by intrinsic defect and graphitic N of N, P co-doped carbon microspheres for BPA degradation - Guojuan Qu; Peng Jia; Tao Zhang; Shuai Tang; Md. Nahid Pervez; Yixiong Pang; Bin Li; Chengjin Cao; Yaping Zhao (Chemical Engineering Journal, 2023)

Sulfur-aided aerobic biostabilization of swine manure and sawdust mixture: Humification and carbon loss - Yang Wang; Jingwen Wang; Guorong Yi; Xuan Wu; Xiu Zhang; Xu Yang; Kuok Ho Daniel Tang; Ran Xiao; Zengqiang Zhang; Guangzhou Qu; Ronghua Li (Bioresource Technology, 2023)

In Silico and Expression Analysis of Papain-Like Cysteine Proteinases (PLCP) Genes in Vitis vinifera to Predict Their Involvement in Hormonal Signaling and Disease Resistance - Ting Zhao; Jing Yan; Ziyang Qu; Ling Wang; Yujin Tang; Chaohong Zhang; Yan Li (Journal of Plant Growth Regulation, 2023)

Simultaneous electrochemical detection of dimethyl bisphenol A and bisphenol A using a novel Pt@SWCNTs-MXene-rGO modified screen-printed sensor - Guangfei Qu; Yun Zhang; Junhong Zhou; Huimin Tang; Wei Ji; Zhoupeng Yan; Keheng Pan; Ping Ning (Chemosphere, 2023)

Synergistic mechanism of formaldehyde adsorption by intrinsic defects and carboxyl groups on the surface of carbon materials - Zekun Sun; Zhonghua Wang; Xue Yang; Kaibo An; Zhibin Qu; Ziyu Tang; Shiwei Lai; Mingqi He; Lei Yang; Bo Zhou; Haiqian Zhao (Chemosphere, 2023)

Solar-driven strongly coupled plasmonic Au nanoarrays on mesoporous silica nanodisks enable selective fungal and bacterial inactivation in well water - Zhuoyun Tang; Dingren Ma; Jingling Yang; Jinjuan Chen; Zhuohang Lin; Qiwen Liang; Yimu Jiao; Wei Qu; Dehua Xia (Water Research, 2023)

Sodium alginate based energy harvesting fibers: Multiscale structure and moist-electrical properties - Rui Zhang; Hai Wang; Meijie Qu; Shuhui Li; Yue Ma; Xinye Li; Ping Tang; Yuezhen Bin (Chemical Engineering Journal, 2023)

A pan-coronavirus peptide inhibitor prevents SARS-CoV-2 infection in mice by intranasal delivery - Lili Wu; Anqi Zheng; Yangming Tang; Yan Chai; Jiantao Chen; Lin Cheng; Yu Hu; Jing Qu; Wenwen Lei; William Jun Liu; Guizhen Wu; Shaogui Zeng; et al. (Science China Life Sciences, 2023)

Comparative study on the removal of 1- naphthol and 2-naphthol by ferrate (VI): Kinetics, reaction mechanisms and theoretical calculations - Yumeng Qi; Yao Yu; Ahmed A. Allam; Jamaan S. Ajarem; Naif G. Altoom; Afzal Ahmed Dar; Xiaosheng Tang; Zunyao Wang; Ruijuan Qu (Chemosphere, 2023)

Insights into oxidation of pentachlorophenol (PCP) by low-dose ferrate(VI) catalyzed with α-Fe2O3 nanoparticles - Boying Liu; Junyan Wei; Shengnan Zhang; Asam Shad; Xiaosheng Tang; Ahmed A. Allam; Zunyao Wang; Ruijuan Qu (Journal of Hazardous Materials, 2023)

Isotope provenance of AMD and treatment options for large, abandoned mines: A case study of the abandoned Dashu pyrite mine, Southwest China - Fang Yang; Zaiwen Yang; Huaidong Zhou; Lu Sun; Aimin Zhang; Yang Li; Lingfei Qu; Liang Tang (Geochemistry, 2023)

Specific response of soil properties to microplastics pollution: A review - Panting Zhang; Ying Yuan; Jia Zhang; Taoyi Wen; Hui Wang; Chengtun Qu; Wenbing Tan; Beidou Xi; Kunlong Hui; Jun Tang (Environmental Research, 2023)

Study on gender differences between male and female Sargassum thunbergii based on metabolomic analysis and physiological functions - Tianyi Qiu; Yan Sun; Tongfei Qu; Song Xue; Jun Chen; Yu Zang; Qian Liu; Xuexi Tang (Algal Research, 2023)

Martynoside rescues 5-fluorouracil-impaired ribosome biogenesis by stabilizing RPL27A - Mengying Hong; Yushen Du; Dongdong Chen; Yuan Shi; Menglong Hu; Kejun Tang; Zhuping Hong; Xiangzhi Meng; Wan Xu; Gaoqi Wu; Yuanyuan Yao; Liubo Chen; et al. (Science Bulletin, 2023)

Early Oligocene gravity-flow deposits at the base of the Meiji Reef system in the South China Sea, and their palaeoclimate significance - Yaobin Sun; Yunfeng Zhang; Yu Tang; Zhenyu Wang; Wen Yan; Weihai Xu; Haizhou Qu; Aihua Xi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Photo-aged non-biodegradable and biodegradable mulching film microplastics alter the interfacial behaviors between agricultural soil and inorganic arsenic - Shuai Tang; Peipei Sun; Guojuan Qu; Yue Tian; Junlai Liu; Md. Nahid Pervez; Xiuyan Li; Chengjin Cao; Yaping Zhao (Journal of Hazardous Materials, 2023)

Effects of climate change and anthropogenic activity on ranges of vertebrate species endemic to the Qinghai–Tibet Plateau over 40 years - Dechun Jiang; Xumao Zhao; Jordi López‐Pujol; Zhiqiang Wang; Yanhua Qu; Yanming Zhang; Tongzuo Zhang; Dayong Li; Ke Jiang; Bin Wang; Chaochao Yan; Jia‐Tang Li (Conservation Biology, 2023)
Over the past 40 years, the climate has been changing and human disturbance has increased in the vast Qinghai–Tibet Plateau (QTP). These 2 factors are expected to affect the distribution of a large number of endemic vertebrate species. However, quantitative relationships between range shifts and climate change and human disturbance of these species in the QTP have rarely been evaluated. We used occurrence records of 19 terrestrial vertebrate species (birds, mammals, amphibians, and reptiles) occurring in the QTP from 1980 to 2020 to quantify the effects of climate change and anthropogenic impacts on the distribution of these 4 taxonomic groups and estimated species range changes in each species. The trend in distribution changes differed among the taxonomic groups, although, generally, ranges shifted to central QTP. Climate change contributed more to range variation than human disturbance (the sum of the 4 climatic variables contributed more than the sum of the 4 human disturbance variables for all 4 taxonomic groups). Suitable geographic range increased for most mammals, amphibians, and reptiles (+27.6%, +18.4%, and +27.8% on average, respectively), whereas for birds range decreased on average by 0.9%. Quantitative evidence for climate change and human disturbance associations with range changes for endemic vertebrate species in the QTP can provide useful insights into biodiversity conservation under changing environments.

Valorisation of food waste for valuable by-products generation with economic assessment - Xietian Zheng; Xikai Chen; Anlan Qu; Wenjing Yang; Lu Tao; Feiyue Li; Jingang Huang; Xiaobin Xu; Junhong Tang; Pingzhi Hou; Wei Han (Journal of Environmental Management, 2023)

Hexachloroplatinic(IV)-GO colloids as ideal electrodes modification materials for electrochemical sensing, HER and OER - Guangfei Qu; Junhong Zhou; Wei Ji; Huimin Tang; Kunling Wei; Yun Zhang; Keheng Pan; Ping Ning (Chemical Engineering Journal, 2023)

Degradation of PCB77 in spiked soils by ferrous sulfide-activated persulfate combined with potassium permanganate - Yue Bu; Nannan Wu; Yumeng Qi; Junyan Wei; Xiaosheng Tang; Ahmed A Allam; Ping Sun; Zunyao Wang; Ruijuan Qu (Chemical Engineering Journal, 2023)

Benzene abatement catalyzed by Ceria-Supported platinum nanoparticles and single atoms - Jing Liu; Xue Fang; Daoqing Liu; Xiaolei Hu; Tian Qin; Junxiao Chen; Rui Liu; Dongrun Xu; Weiye Qu; Yangyang Dong; Liwei Chen; Zhen Ma; et al. (Chemical Engineering Journal, 2023)

Divergent contributions of coding and noncoding sequences to initial high‐altitude adaptation in passerine birds endemic to the Qinghai–Tibet Plateau - Yan Hao; Gang Song; Yong E. Zhang; Weiwei Zhai; Chenxi Jia; Yanzhu Ji; Shiyu Tang; Hongrui Lv; Yanhua Qu; Fumin Lei (Molecular Ecology, 2023)
Early events in the evolution of an ancestral lineage can shape the adaptive patterns of descendant species, but the evolutionary mechanisms driving initial adaptation from an ancestor remain largely unexplored. High‐altitude adaptations have been extensively explored from the viewpoint of protein‐coding genes; however, the contribution of noncoding regions remains relatively neglected. Here, we integrate genomic and transcriptomic data to investigate adaptive evolution in the ancestor of three high‐altitude snowfinch species endemic to the Qinghai–Tibet Plateau. Our genome‐wide scan for adaptation in the snowfinch ancestor identifies strong adaptation signals in functions of development and metabolism for the coding genes, but in functions of the nervous system development for noncoding regions. This pattern is exclusive to the snowfinch ancestor compared to a control ancestral lineage subject to weak selection. Changes in noncoding regions in the snowfinch ancestor, especially those nearest to coding genes, may be disproportionately associated with the differential expression of genes in the brain tissue compared to other tissues. Extensive gene expression in the brain tissue can be further altered via genetic regulatory networks of transcription factors harbouring potential accelerated regulatory regions (e.g., the development‐related transcription factor YEATS4 ). Altogether, our study provides new evidence concerning how coding and noncoding sequences work through decoupled pathways in initial adaptation to the selective pressure of high‐altitude environments. The analysis highlights the idea that noncoding sequences may be promising elements in facilitating the rapid evolution and adaptation to high altitudes.

Fe contents and isotopes in suspended particulate matter of Lancang River in Southwest China - Yang Tang; Guilin Han; Liu Man; Jie Zeng; Rui Qu (Science of The Total Environment, 2023)

Photochemical transformation of anthracene (ANT) in surface soil: Chlorination and hydroxylation - Zhengnan Tu; Yumeng Qi; Xiaosheng Tang; Zunyao Wang; Ruijuan Qu (Journal of Hazardous Materials, 2023)

ARPC5 is transcriptionally activated by KLF4, and promotes cell migration and invasion in prostate cancer via up-regulating ADAM17 - GenYi Qu; YuLong Zhang; HongTao Duan; Cheng Tang; Guang Yang; Dan Chen; Yong Xu (Apoptosis, 2023)

Formation processes and source contributions of ground‐level ozone in urban and suburban Beijing using the WRF‐CMAQ modelling system - Shuxian Zhang; Zhongzhi Zhang; Yang Li; Xiaohui Du; Linglu Qu; Wei Tang; Jun Xu; Fan Meng (Journal of Environmental Sciences, 2023)

Effects of chitosan coating combined with thermal treatment on physicochemical properties, bacterial diversity and volatile flavor of braised duck meat during refrigerated storage - Huanhuan Li; Sijia Qu; Ping Ma; Jin Zhang; Ke Zhao; Lihong Chen; Qicheng Huang; Gaohang Zou; Honggang Tang (Food Research International, 2023)

Correction of sub-seasonal predictions of summer precipitation in Southwest China based on the Transformer-Seq2Seq-DNN ensemble deep learning model - Qu Guo; Fei Luo; Hongyu Tang; Yonghua Li (Theoretical and Applied Climatology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Hydrothermal alteration and corresponding reservoir significance of the Permian Emeishan basaltic lavas, west Sichuan, China - Y. B. Sun; Y. F. Zhang; A. H. Xi; Y. Tang; B. J. Zhang; S. Q. Pei; R. R. Li; H. Yin; Q. Zeng; H. Z. Qu; R. J. Zhou (Australian Journal of Earth Sciences, 2023)

Synthesis of a low temperature ionic liquid demulsifier and its demulsification mechanism - Liwei Shen; Shi Liu; Ji'an He; Qian Qu; Yuqi Tang; Zejun Zhang; Dong Xiang; Xuemin Yan; Yuanzhu Mi (Fuel, 2023)

Synthesis of a multi-branched trinuclear ionic liquid demulsifier and evaluation of its performance in W/O emulsions - Zejun Zhang; Zhansheng Wang; Qingji Wang; Hua Zhang; Yuqi Tang; Qian Qu; Liwei Shen; Dong Xiang; Yuanzhu Mi; Xuemin Yan (Fuel, 2023)

The relationships between heavy metals and bacterial communities in a coal gangue site - Bing Kou; Yue He; Yang Wang; Chengtun Qu; Jun Tang; Yuman Wu; Wenbing Tan; Ying Yuan; Tingqiao Yu (Environmental Pollution, 2023)

Aggregation-induced color fine-tunable carbon dot phosphorescence covering from green to near-infrared for advanced information encryption - Qijun Li; Dengke Cheng; Hailing Gu; Daiqi Yang; Yuchen Li; Shuai Meng; Yunyang Zhao; Zikang Tang; YiBo Zhang; Jing Tan; Songnan Qu (Chemical Engineering Journal, 2023)

Major and stably expressed QTL for traits related to the mature wheat embryo independent of kernel size - Surong Wang; Tianyu Wang; Qijing Xuan; Xiangru Qu; Qiang Xu; Qiantao Jiang; Zhien Pu; Yang Li; Yunfeng Jiang; Guoyue Chen; Mei Deng; Yanling Liu; et al. (Theoretical and Applied Genetics, 2023)

Production of MSTN knockout porcine cells using adenine base-editing-mediated exon skipping - Shuai-peng Yang; Xiang-xing Zhu; Zi-xiao Qu; Cai-yue Chen; Yao-bing Wu; Yue Wu; Zi-dan Luo; Xin-yi Wang; Chu-yu He; Jia-wen Fang; Ling-qi Wang; Guang-long Hong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2023)

Pyrolysis temperature affects the physiochemical characteristics of lanthanum-modified biochar derived from orange peels: Insights into the mechanisms of tetracycline adsorption by spectroscopic analysis and theoretical calculations - Zhihao Chen; Bingfeng Lin; Yingping Huang; Yanbiao Liu; Yonghong Wu; Rui Qu; Cilai Tang (Science of The Total Environment, 2023)

Effect of oxygen functional groups on competitive adsorption of benzene and water on carbon materials: Density functional theory study - Haiqian Zhao; Ziyu Tang; Mingqi He; Xue Yang; Shiwei Lai; Kaibo An; Shuaishuai Han; Zhibin Qu; Wei Zhou; Zhonghua Wang (Science of The Total Environment, 2023)

Polystyrene nanoplastics inhibit StAR expression by activating HIF-1α via ERK1/2 MAPK and AKT pathways in TM3 Leydig cells and testicular tissues of mice - Aiyi Sui; Chenjuan Yao; Yanhong Chen; Yanli Li; Shali Yu; Jianhua Qu; Haiyan Wei; Juan Tang; Gang Chen (Food and Chemical Toxicology, 2023)

Natural-human driving factors of groundwater salinization in a long-term irrigation area - Yuting Zhang; Kai Hou; Hui Qian; Yanyan Gao; Yuan Fang; Shunqi Tang; Shan Xiao; Wenhao Ren; Wengang Qu; Qiying Zhang (Environmental Research, 2023)

Quantification of enhanced nitrogen removal pathways of pyrite interaction with anammox sludge system - Fan Feng; Caiyan Qu; Jia Tang; Xing Wu; Xi Tang; Fubing Yao; Liyuan Chai; Ruiyang Xiao; Chong-Jian Tang (Chemical Engineering Journal, 2023)

Low expression of miR-1929-3p mediates murine cytomegalovirus-induced fibrosis in cardiac fibroblasts via targeting endothelin a receptor/NLRP3 inflammasome pathway - Jiayi Li; Yongjia Wang; LaMei Wang; Yuanyuan Qu; Wei Zhou; Hua Zhong; DongMei Xi; Na Tang; Fang He (In Vitro Cellular & Developmental Biology - Animal, 2023)

Genetic relationship between granite and pegmatite in the Kaluan lithium deposit, Western China: evidence from the inversion of audio-magnetotelluric data - You-Heng Qu; Bin Hu; Bin Tang; Chao-Feng Wu; Feng Zhou (Applied Geophysics, 2023)

Dosing with pyrite significantly increases anammox performance: Its role in the electron transfer enhancement and the functions of the Fe-N-S cycle - Fan Feng; Zhigong Liu; Xi Tang; Xing Wu; Caiyan Qu; Seow Wah How; Di Wu; Ruiyang Xiao; Chong-Jian Tang; Zhang Lin; Liyuan Chai; Guang-Hao Chen (Water Research, 2023)

Constructing model-averaging species sensitivity distributions of Phenanthrene based on reproductive fitness: Implications for assessing ecological risk in urban watershed - Zefan Wang; Chengkai Qu; Jiawei Zhang; Lihao Zhi; Tiandong Tang; Huang Yao; Wenping Li; Changhe Shi; Shihua Qi (Journal of Hazardous Materials, 2023)

Hydrogen/PRF skeletal mechanism study based on shock tube experiments and kinetic analysis - Wenjing Qu; Yuan Fang; Zixin Wang; Meijia Song; Qiukai Wang; Bin Tang; Liyan Feng (Fuel, 2023)

Air pollutant emissions and reduction potentials from municipal solid waste incineration in China - Ling Tang; Jing Guo; Ruxing Wan; Min Jia; Jiabao Qu; Ling Li; Xin Bo (Environmental Pollution, 2023)

Novel supported low-temperature solid molten salt (SMS) anode materials for Li-ion batteries - Lei Jiang; Ning Han; Tingting Luo; Zhe Zhang; Fenghao Liang; Daoning Wu; Xiaochun Li; Fengjiao Liu; Yichuan Rui; Wei Zhang; Yi Qu; Bohejin Tang (Chemical Engineering Journal, 2023)

Regulating the charge densities of s-Block calcium single-atom site catalysts for efficient N2 activation and reduction - Tianyong Liu; Xiaoyang Qu; Yuqin Zhang; Xiaohang Wang; Qian Dang; Xingxing Li; Binju Wang; Shaobin Tang; Yi Luo; Jun Jiang (Chemical Engineering Journal, 2023)

Structure–performance correlation guided cerium-based metal–organic frameworks: Superior adsorbents for fluoride removal in water - Xiaofeng Tang; Wu Xia; Xiaolin Qu; Chaohai Wang; Wenjun Wang; Yuntao Liang; Yuxi Zeng; Weiping Xiong; Min Cheng; Biao Song; Chengyun Zhou; Xiaoying Zhao (Chemosphere, 2023)

Cadmium impairs the development of natural killer cells and bidirectionally modifies their capacity for cytotoxicity - Yufan Zhang; Yifan Zhao; Yue Zhai; Jinyi He; Mengke Tang; Yalin Liu; Ye Yao; Peng Xue; Miao He; Qian Li; Yanyi Xu; Weidong Qu; et al. (Chemosphere, 2023)

Charge instability of topological Fermi arcs in chiral crystal CoSi - Zhicheng Rao; Quanxin Hu; Shangjie Tian; Qing Qu; Congrun Chen; Shunye Gao; Zhenyu Yuan; Cenyao Tang; Wenhui Fan; Jierui Huang; Yaobo Huang; Li Wang; et al. (Science Bulletin, 2023)

Experimental study on non-isothermal oxidative characteristics and kinetics of methane in accelerating rate calorimetry tests - Xiaodong Tang; Wanfen Pu; Dan Wang; Shanshan Qu; Yiming Rui; Xuepei Zhao; Renbao Liu (Fuel, 2023)

Subcutaneous injection of a bortezomib-loaded thermosensitive hydrogel for the treatment of multiple myeloma - Ying Qu; Bingyang Chu; Kun Shi; Xue Wei; Peipei Yang; Mengran Chen; Minghai Tang; Shiqian Li; Fangfang Wang; Xijing Yang; Yuhuan Zheng; Ting Niu; et al. (Chemical Engineering Journal, 2023)

Arsenic trioxide promotes ERK1/2-mediated phosphorylation and degradation of BIMEL to attenuate apoptosis in BEAS-2B cells - Yilun Liang; Yun Qian; Jing Tang; Chenjuan Yao; Shali Yu; Jianhua Qu; Haiyan Wei; Gang Chen; Yu Han (Chemico-Biological Interactions, 2023)

Phycospheric bacterial community structure and function succession during the typical harmful macroalgal blooms - Tongfei Qu; Chengzong Hou; Chen Guan; Xinyu Zhao; Jun Chen; Yi Zhong; Jinhui Xu; Zhihao Lin; Yu Xu; Xuexi Tang; Ying Wang (Frontiers in Marine Science, 2022)
Based on the diversity and importance of phycospheric microorganisms as well as their complex interaction with algae, their ecological correlation with algal bloom events has become a research topic of great interest that remains unclear in the natural dynamic process of harmful macroalgal blooms (HMBs). The world’s largest green tides caused by macroalgae Ulva prolifera have occurred in the Yellow Sea for 16 consecutive years, and seriously affected the coastal ecosystem. Here, we monitored the spatiotemporal dynamics of the phycospheric bacterial community during the U . prolifera green tide bloom. The 73-day continuous field survey covered the whole process of initial invasion until the extinction of the green tide. The phycospheric bacterial community has a higher richness than the control seawater bacteria; in addition, it has more enriched taxa with organic nutrition preference and environmental pressure adaption, such as Bacteroidetes, Firmicutes, and Desulfobacterota. The same differences in populations and functional profiles were observed among the epiphytic bacterial and phycospheric seawater bacterial communities, which may be driven by the spatial heterogeneity of biogenic elements (e.g., organic nutrients and oxygen) among the habitats. Significant succession occurred in both the epiphytic bacterial and phycospheric seawater bacterial communities; their diversity and richness exhibited significant heterogeneity variation patterns, and their community structure became more similar in late phases. Our study revealed that macroalgal phycospheric microbial communities have a highly complex and dynamic composition and variable ecological functions, which indicate that phycospheric microorganisms are closely related to the fate of HMBs and may have the profound effect coastal biogeochemical cycles.

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Iron metabolism, ferroptosis, and lncRNA in cancer: knowns and unknowns - Lei Qu; Xinyu He; Qian Tang; Xiao Fan; Jian Liu; Aifu Lin (Journal of Zhejiang University-SCIENCE B, 2022)

Functional analysis of HADH c.99C>G shows that the variant causes the proliferation of pancreatic islets and leu-sensitive hyperinsulinaemia - Wu Long; Yue-Bing Wang; Peng-Fei Qu; Lin Ma; Si-Jie Wei; Yan-Mei Xi; Jin-Liang Du; Xue Tang; Kai Liu; Yu-Hua Li; Pu-Ping Lei (Journal of Genetics, 2022)

Deletions in GSN gene associated with growth traits of four Chinese cattle breeds - Ao Qi; Wenxiu Ru; Yangkai Liu; Yu Yang; Jia Tang; Haiyan Yang; Shuling Yang; Kaixing Qu; Xianyong Lan; Chuzhao Lei; Bizhi Huang; Hong Chen (Molecular Genetics and Genomics, 2022)

Quick mapping and characterization of a co-located kernel length and thousand-kernel weight-related QTL in wheat - Xiangru Qu; Cong Li; Hang Liu; Jiajun Liu; Wei Luo; Qiang Xu; Huaping Tang; Yang Mu; Mei Deng; Zhien Pu; Jun Ma; Qiantao Jiang; et al. (Theoretical and Applied Genetics, 2022)

The IRE1/JNK signaling pathway regulates inflammation cytokines and production of glomerular extracellular matrix in the acute kidney injury to chronic kidney disease transition - Yan Liang; Lingyun Qu; Zhenjie Liu; Lulu Liang; Yingzi Wang; Songxia Quan; Yulin Wang; Lin Tang (Molecular Biology Reports, 2022)

Degradation mechanism of HCN by electrochemically coupled copper-loaded magnetic nanoparticles in a liquid phase pseudo-homogeneous system - Guangfei Qu; Wei Ji; Junyan Li; Shuaiyu Liang; Zhishuncheng Li; Huimin Tang; Junhong Zhou; Ping Ning (Environmental Science and Pollution Research, 2022)

Multi-omics analysis reveals the mechanism of seed coat color formation in Brassica rapa L. - Huiyan Zhao; Guoxia Shang; Nengwen Yin; Si Chen; Shulin Shen; Haiyan Jiang; Yunshan Tang; Fujun Sun; Yuhan Zhao; Yongchao Niu; Zhi Zhao; Liang Xu; et al. (Theoretical and Applied Genetics, 2022)

Characteristics of Complex Fractures by Liquid Nitrogen Fracturing in Brittle Shales - Hai Qu; Shimao Tang; Ying Liu; Pengpeng Huang; Xiaoguang Wu; Zhonghua Liu; Chengying Li (Rock Mechanics and Rock Engineering, 2022)

Acoustic Emission and Failure Characteristics of Shales with Different Brittleness Under AWJ Impingement - Hai Qu; Xiaoguang Wu; Pengpeng Huang; Shimao Tang; Rui Wang; Yushuang Hu (Rock Mechanics and Rock Engineering, 2022)

Numerical Simulation of Rock Thermal Fracture Considering Friction Effect in the Framework of Smooth Particle Hydrodynamics Based on Total Lagrangian Formula - Dianrui Mu; Dongyu Zhang; Aiping Tang; Haigang Qu; Zhiming Li (Rock Mechanics and Rock Engineering, 2022)

Adenine base-editing-mediated exon skipping induces gene knockout in cultured pig cells - Xiang-xing Zhu; Jia-sheng Pan; Tao Lin; Ye-cheng Yang; Qiu-yan Huang; Shuai-peng Yang; Zi-xiao Qu; Zi-sheng Lin; Jian-cong Wen; Ai-fen Yan; Juan Feng; Lian Liu; et al. (Biotechnology Letters, 2022)

Maternal intake of caffeinated products and birth defects: a systematic review and meta-analysis of observational studies - Yan Yue; Wenxing Li; Jun Tang; Yan Zeng; Tao Xiong; Xia Qiu; Jing Shi; Hua Wang; Bin Xia; Lili Luo; Yi Qu; Dezhi Mu (Critical Reviews in Food Science and Nutrition, 2021)

Cytotoxic triterpenoid glycosides from leaves of Cyclocarya paliurus - Hui-Hui Sun; Wen-Yan Lv; Jie Tan; Yu-Cheng Tang; Hui Zhu; Jian-Bo Qu; Jing Li; Jian-Ping Wu; Xi-Wen Chang; Zhi-Chun Yang; Wen-Xuan Wang; Zu-Hui Chen; et al. (Natural Product Research, 2021)

Comparison of environmental responding strategies between Ulva prolifera and Sargassum horneri: an in-situ study during the co-occurrence of green tides and golden tides in the Yellow Sea, China in 2017 - Xinyu Zhao; Yi Zhong; Huanxin Zhang; Tongfei Qu; Chengzong Hou; Chen Guan; Feng Liu; Xuexi Tang; Ying Wang (Journal of Oceanology and Limnology, 2021)

An eco‐city design methodology for hilly areas of western China - Kai Lin; Zhengwei He; Zhujun Zhao; Jiaxin Chang; Keran Tang; Rui Qu; Li He (Earth Science Informatics, 2021)

Prediction and correction of in situ summer precipitation in Southwest China based on a downscaling method with the BCC_CSM - Qu Guo; Xiangwen Liu; Hongyu Tang; Yonghua Li (Theoretical and Applied Climatology, 2021)

Transcriptome Analysis of Nitrogen Metabolism, Transcription Factors, and Indigoid Biosynthesis in Isatis indigotica Fort. Response to Nitrogen Availability - Renjun Qu; Yiwen Cao; Huibo Zhang; Yujing Miao; Lian Wei; Xiaoqing Tang; Liqiong Sun (Journal of Plant Growth Regulation, 2021)

Investigation of the decline of Ulva prolifera in the Subei Shoal and Qingdao based on physiological changes - Ya Hao; Chen Guan; Xinyu Zhao; Tongfei Qu; Xuexi Tang; Ying Wang (Journal of Oceanology and Limnology, 2021)

Unraveling Physiological and Metabolomic Responses Involved in Phlox subulata L. Tolerance to Drought Stress - Yan Xiong; Yanting Qu; Hui Han; Fei Chen; Li Li; Huanwei Tang; Daidi Che; Xing Zhang (Plant Molecular Biology Reporter, 2021)

Extreme storm surges and waves and vulnerability of coastal bridges in New York City metropolitan region: an assessment based on Hurricane Sandy - K. Qu; W. Yao; H. S. Tang; A. Agrawal; G. Shields; S. I. Chien; S. Gurung; Y. Imam; I. Chiodi (Natural Hazards, 2021)

Physiological Responses of Highland Barley Seedlings to NaCl, Drought, and Freeze-Thaw Stress - Yixin Chang; Jitao Zhang; Guozhang Bao; Bairu Yan; Yan Qu; Mengyu Zhang; Wenyi Tang (Journal of Plant Growth Regulation, 2021)

Default mode network integrity changes contribute to cognitive deficits in subcortical vascular cognitive impairment, no dementia - Qi Qin; Yi Tang; Xuejiao Dou; Yida Qu; Yi Xing; Jianwei Yang; Tianshu Chu; Yong Liu; Jianping Jia (Brain Imaging and Behavior, 2021)

Post-failure landslide change detection and analysis using optical satellite Sentinel-2 images - Feihang Qu; Haijun Qiu; Hesheng Sun; Minggao Tang (Landslides, 2021)

Short-term exposure to air pollution and occurrence of emergency stroke in Chongqing, China - Caizhi Tang; Yu Chen; Qiaoling Song; Jianfei Ma; Ying Zhou; Liang Gong; Xingshu Chen; Jifu Qu; Yongjun Luo (International Archives of Occupational and Environmental Health, 2021)

Correction to: Evolutionary and recombination analysis of porcine reproductive and respiratory syndrome isolates in China - Zhendong Zhang; Xiangyang Qu; Hongliang Zhang; Xudong Tang; Ting Bian; Yingjun Sun; Mingming Zhou; Fubo Ren; Ping Wu (Virus Genes, 2020)

A novel, major, and validated QTL for the effective tiller number located on chromosome arm 1BL in bread wheat - Jiajun Liu; Huaping Tang; Xiangru Qu; Hang Liu; Cong Li; Yang Tu; Shuiqing Li; Ahsan Habib; Yang Mu; Shoufeng Dai; Mei Deng; Qiantao Jiang; et al. (Plant Molecular Biology, 2020)

MicroRNA-153-3p enhances the sensitivity of chronic myeloid leukemia cells to imatinib by inhibiting B-cell lymphoma-2-mediated autophagy - Yu-Ling Li; Jia-Ming Tang; Xiao-Yun Chen; Bing Luo; Guo-Hua Liang; Qian Qu; Zi-Yuan Lu (Human Cell, 2020)

Evolutionary and recombination analysis of porcine reproductive and respiratory syndrome isolates in China - Zhendong Zhang; Xiangyang Qu; Hongliang Zhang; Xudong Tang; Ting Bian; Yingjun Sun; Mingming Zhou; Fubo Ren; Ping Wu (Virus Genes, 2020)

Identification and characterization of mRNAs and lncRNAs of a barley shrunken endosperm mutant using RNA-seq - Yaya Zou; Huaping Tang; Ting Li; Min Sun; Xiangru Qu; Jieguang Zhou; Congcong Yang; Yang Mu; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Guangdeng Chen; et al. (Genetica, 2020)

Selenium Mitigates Cadmium-Induced Adverse Effects on Trace Elements and Amino Acids Profiles in Chicken Pectoral Muscles - Kui-Chao Qu; Hui-Qin Li; Kou-Kou Tang; Zhen-Yong Wang; Rui-Feng Fan (Biological Trace Element Research, 2020)

Insights into the regulatory characteristics of silkworm fibroin gene promoters using a modified Gal4/UAS system - Rongpeng Liu; Wenhui Zeng; Tingting Tan; Tao Chen; Qin Luo; Dawei Qu; Yiyun Tang; Dingpei Long; Hanfu Xu (Transgenic Research, 2019)

Adsorption of Ni2+ and Pb2+ from water using diethylenetriamine-grafted Spirodela polyrhiza: behavior and mechanism studies - Wei Qu; Deliang He; Yanni Guo; Yining Tang; Jun Shang; Lei Zhou; Rilong Zhu; Ren-Jie Song (Environmental Science and Pollution Research, 2019)

Selenium alleviates cadmium-induced inflammation and meat quality degradation via antioxidant and anti-inflammation in chicken breast muscles - Kou-Kou Tang; Hui-Qin Li; Kui-Chao Qu; Rui-Feng Fan (Environmental Science and Pollution Research, 2019)

Characterization of modified Alternanthera philoxeroides by diethylenetriamine and its application in the adsorption of copper(II) ions in aqueous solution - Wei Qu; Deliang He; Yanni Guo; Yining Tang; Ren-Jie Song (Environmental Science and Pollution Research, 2019)

Cefquinome-Loaded Microsphere Formulations in Protection against Pneumonia with Klebsiella pneumonia Infection and Inflammatory Response in Rats - Shaoqi Qu; Cunchun Dai; Fenfang Yang; Tingting Huang; Zhihui Hao; Qihe Tang; Haixia Wang; Yanping Zhang (Pharmaceutical Research, 2019)

Distribution of ancient α1 and α2 domain lineages between two classical MHC class I genes and their alleles in grass carp - Zibin Li; Nan Zhang; Lizhen Ma; Zehui Qu; Xiaohui Wei; Zixin Liu; Minghu Tang; Nianzhi Zhang; Yinan Jiang; Chun Xia (Immunogenetics, 2019)

Photosynthetic response of floating Ulva prolifera to diurnal changes of in-situ environments on the sea surface - Xinyu Zhao; Xuexi Tang; Shunxin Hu; Yi Zhong; Tongfei Qu; Ying Wang (Journal of Oceanology and Limnology, 2019)

Bacterial communities fluctuate in abundance and diversity under simulated oil-contaminated seawater conditions - Xiaohong Li; Cai You; Liang Qu; Bin Zhou; Xuexi Tang; Hui Xiao (Journal of Oceanology and Limnology, 2019)

Treatment of fracturing fluid waste by Fenton reaction using transition metal complexes catalyzes oxidation of hydroxypropyl guar gum at high pH - Ying Tang; Haomiao Ren; Pengwei Yang; Hong Li; Jie Zhang; Chengtun Qu; Gang Chen (Environmental Chemistry Letters, 2019)

The effects of air temperature and precipitation on the net primary productivity in China during the early 21st century - Qianfeng Wang; Jingyu Zeng; Song Leng; Bingxiong Fan; Jia Tang; Cong Jiang; Yi Huang; Qing Zhang; Yanping Qu; Wulin Wang; Wei Shui (Frontiers of Earth Science, 2018)

Knockout of ush2a gene in zebrafish causes hearing impairment and late onset rod-cone dystrophy - Shanshan Han; Xiliang Liu; Shanglun Xie; Meng Gao; Fei Liu; Shanshan Yu; Peng Sun; Changquan Wang; Stephen Archacki; Zhaojing Lu; Xuebin Hu; Yayun Qin; et al. (Human Genetics, 2018)

Distribution, relationship, and risk assessment of toxic heavy metals in walnuts and growth soil - Yongxiang Han; Zhanglin Ni; Shiliang Li; Minghua Qu; Fubin Tang; Runhong Mo; Caifen Ye; Yihua Liu (Environmental Science and Pollution Research, 2018)

Generation and Screening of T-DNA Insertion Mutants Mediated by Agrobacterium tumefaciens in the Garden Asparagus Stem Blight Pathogen Phomopsis asparagi - Yueping Zhang; Huaxiang Qu; Ping Zhao; Yongping Tang; Jingsong Zhou; Shaochun Luo; Yuling Yin; Guangyu Chen (Current Microbiology, 2017)

Peripheral Lymphocyte Subsets as a Marker of Parkinson’s Disease in a Chinese Population - Luan Cen; Chaohao Yang; Shuxuan Huang; Miaomiao Zhou; Xiaolu Tang; Kaiping Li; Wenyuan Guo; Zhuohua Wu; Mingshu Mo; Yousheng Xiao; Xiang Chen; Xinling Yang; et al. (Neuroscience Bulletin, 2017)

Microbial community composition and electricity generation in cattle manure slurry treatment using microbial fuel cells: effects of inoculum addition - Binghan Xie; Weijia Gong; An Ding; Huarong Yu; Fangshu Qu; Xiaobin Tang; Zhongsen Yan; Guibai Li; Heng Liang (Environmental Science and Pollution Research, 2017)

Effect of oxidative stress from nanoscale TiO2 particles on a Physarum polycephalum macroplasmodium under dark conditions - Zhi Zhang; Jianhua Zhang; Caixia Shi; Heng Guo; RuiYang Ni; Junle Qu; Jiaoning Tang; Shide Liu (Environmental Science and Pollution Research, 2017)

Genetic mapping of QTL for the sizes of eight consecutive leaves below the tassel in maize (Zea mays L.) - Cong Yang; Dengguo Tang; Jingtao Qu; Ling Zhang; Lei Zhang; Zhengjie Chen; Jian Liu (Theoretical and Applied Genetics, 2016)

Effect of operation parameters on the flux stabilization of gravity-driven membrane (GDM) filtration system for decentralized water supply - Xiaobin Tang; An Ding; Fangshu Qu; Ruibao Jia; Haiqing Chang; Xiaoxiang Cheng; Bin Liu; Guibai Li; Heng Liang (Environmental Science and Pollution Research, 2016)

Levels and distribution of organochlorine pesticides and hexachlorobutadiene in soils and terrestrial organisms from a former pesticide-producing area in Southwest China - Zhenwu Tang; Qifei Huang; Zhiqiang Nie; Yufei Yang; Jun Yang; Dan Qu; Jiali Cheng (Stochastic Environmental Research and Risk Assessment, 2016)

PI3K/Akt/FoxO3a signaling mediates cardioprotection of FGF-2 against hydrogen peroxide-induced apoptosis in H9c2 cells - Mi-Hua Liu; Guo-Hua Li; Li-Jun Peng; Shun-Lin Qu; Yuan Zhang; Juan Peng; Xin-Yuan Luo; Heng-Jing Hu; Zhong Ren; Yao Liu; Hui Tang; Lu-Shan Liu; et al. (Molecular and Cellular Biochemistry, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Unambiguous combined correlation functions for sine-BOC signal tracking - Tao Yan; Jiaolong Wei; Zuping Tang; Bo Qu; Zhihui Zhou (GPS Solutions, 2015)

Evolution process of sediment supply for debris flow occurrence in the Longchi area of Dujiangyan City after the Wenchuan earthquake - Ming Chang; Chuan Tang; Huayong Ni; Yongping Qu (Landslides, 2015)

Computational Fluid Dynamics Study of Bifurcation Aneurysms Treated with Pipeline Embolization Device: Side Branch Diameter Study - Abraham Yik-Sau Tang; Wai-Choi Chung; Eric Tian-Yang Liu; Jie-Qiong Qu; Anderson Chun-On Tsang; Gilberto Ka-Kit Leung; Kar-Ming Leung; Alfred Cheuk-Hang Yu; Kwok-Wing Chow (Journal of Medical and Biological Engineering, 2015)

Division of the stages of coalbed methane desorption based on the Langmuir adsorption isotherm - Meng YanJun; Tang DaZhen; Qu YingJie; Xu Hao; Li Yong (Arabian Journal of Geosciences, 2015)

Effects of Olanzapine–Fluoxetine Combination Treatment of Major Depressive Disorders on the Quality of Life During Acute Treatment Period - Wei Qu; Shanshan Gu; Han Luo; Qianying Tang; Junwei Guo (Cell Biochemistry and Biophysics, 2014)

Impacts of uncertainty in AVOC emissions on the summer ROx budget and ozone production rate in the three most rapidly-developing economic growth regions of China - Feng Wang; Junling An; Ying Li; Yujia Tang; Jian Lin; Yu Qu; Yong Chen; Bing Zhang; Jing Zhai (Advances in Atmospheric Sciences, 2014)

Distal-less homeobox 2 promotes the osteogenic differentiation potential of stem cells from apical papilla - Binbin Qu; Ousheng Liu; Xiaodan Fang; Haixia Zhang; Yuehong Wang; Hongzhi Quan; Jie Zhang; Jing Zhou; Jun Zuo; Jianxia Tang; Zhangui Tang (Cell and Tissue Research, 2014)

Interaction between Chlorella vulgaris and bacteria: interference and resource competition - Liang Qu; Renjun Wang; Peng Zhao; Ruinan Chen; Wenli Zhou; Liuqing Tang; Xuexi Tang (Acta Oceanologica Sinica, 2014)

Effects of PTHrP on chondrocytes of sika deer antler - Bin Guo; Shou-Tang Wang; Cui-Cui Duan; Dang-Dang Li; Xue-Chao Tian; Qu-Yuan Wang; Zhan-Peng Yue (Cell and Tissue Research, 2013)

Vulnerability of population and transportation infrastructure at the east bank of Delaware Bay due to coastal flooding in sea-level rise conditions - Han Song Tang; Steven I-Jy Chien; Marouane Temimi; Cheryl Ann Blain; Qu Ke; Liuhui Zhao; Simon Kraatz (Natural Hazards, 2013)

Expression and regulation of Runx3 in mouse uterus during the peri-implantation period - Zhi-Kun Bai; Bin Guo; Xue-Chao Tian; Dang-Dang Li; Shou-Tang Wang; Hang Cao; Qu-Yuan Wang; Zhan-Peng Yue (Journal of Molecular Histology, 2013)

HBx and HBs regulate RhoC expression by upregulating transcription factor Ets-1 - Dongdong Qin; Kai Li; Jialin Qu; Sen Wang; Chengcheng Zou; Yanrui Sheng; Ailong Huang; Hua Tang (Archives of Virology, 2013)

Screening Key Genes and Pathways in Glioma Based on Gene Set Enrichment Analysis and Meta-analysis - Yanyan Tang; Wenwu He; Yunfei Wei; Zhanli Qu; Jinming Zeng; Chao Qin (Journal of Molecular Neuroscience, 2013)

Finer resolution observation and monitoring of global land cover: first mapping results with Landsat TM and ETM+ data - Peng Gong; Jie Wang; Le Yu; Yongchao Zhao; Yuanyuan Zhao; Lu Liang; Zhenguo Niu; Xiaomeng Huang; Haohuan Fu; Shuang Liu; Congcong Li; Xueyan Li; et al. (International Journal of Remote Sensing, 2013)

Hepatitis B virus regulation of Raf1 promoter activity through activation of transcription factor AP-2α - Jialin Qu; Jianbo Li; Ke Chen; Dongdong Qin; Kai Li; Yanrui Sheng; Chengcheng Zou; Sen Wang; Ailong Huang; Hua Tang (Archives of Virology, 2013)

Enhancements of major aerosol components due to additional HONO sources in the North China Plain and implications for visibility and haze - Junling An; Ying Li; Yong Chen; Jian Li; Yu Qu; Yujia Tang (Advances in Atmospheric Sciences, 2013)

Integrin β8 Signaling in Neonatal Hypoxic–Ischemic Brain Injury - Li Zhang; Yi Qu; Binzhi Tang; Fengyan Zhao; Tao Xiong; Donna Ferriero; Dezhi Mu (Neurotoxicity Research, 2012)

Molybdenite Re–Os and muscovite 40Ar/39Ar dating of quartz vein-type W–Sn polymetallic deposits in Northern Guangdong, South China - Hua-Wen Qi; Rui-Zhong Hu; Xiao-Fei Wang; Wen-Jun Qu; Xian-Wu Bi; Jian-Tang Peng (Mineralium Deposita, 2012)

Proliferation and Differentiation of Neural Stem Cells Are Selectively Regulated by Knockout of Cyclin D1 - Junfang Ma; Zhiyuan Yu; Wensheng Qu; Yingxin Tang; Yan Zhan; Can Ding; Wei Wang; Minjie Xie (Journal of Molecular Neuroscience, 2010)

Activity of Wind-Blown Sand and the Formation of Feathered Sand Ridges in the Kumtagh Desert, China - Kongtai Liao; Jianjun Qu; Jinnian Tang; Feng Ding; Hujun Liu; Shujuan Zhu (Boundary-Layer Meteorology, 2010)

Synthesis and primary evaluation of quinoxalinone derivatives as potent modulators of multidrug resistance - Hongyu Yuan; Xun Li; Xianjun Qu; Lirui Sun; Wenfang Xu; Wei Tang (Medicinal Chemistry Research, 2009)

Des-γ-carboxy prothrombin stimulates human vascular endothelial cell growth and migration - Su-Bo Wang; Yan-Na Cheng; Shu-Xiang Cui; Julia Li Zhong; S. G. Ward; Li-Rui Sun; Ming-Hui Chen; Norihiro Kokudo; Wei Tang; Xian-Jun Qu (Clinical & Experimental Metastasis, 2009)

Introduction of a seedling production method using vegetative gametophytes to the commercial farming of Laminaria in China - Bo Xu; Quan Sheng Zhang; Shan Cun Qu; Yi Zhou Cong; Xue Xi Tang (Journal of Applied Phycology, 2009)

Spatial distribution of benthic algae in the Gangqu River, Shangrila, China - Naicheng Wu; Tao Tang; Xiaodong Qu; Qinghua Cai (Aquatic Ecology, 2009)

Identification and Experimental Verification of Protective Antigens Against Streptococcus suis Serotype 2 Based on Genome Sequence Analysis - Lina Liu; Gong Cheng; Changjun Wang; Xiuzhen Pan; Yanguang Cong; Qu Pan; Jing Wang; Feng Zheng; Fuquan Hu; Jiaqi Tang (Current Microbiology, 2009)

High throughput culture and gametogenesis induction of Laminaria japonica gametophyte clones - Quan Sheng Zhang; Shan Cun Qu; Yi Zhou Cong; Shi Ju Luo; Xue Xi Tang (Journal of Applied Phycology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Breeding of an elite Laminaria variety 90-1 through inter-specific gametophyte crossing - Quan-Sheng Zhang; Xue-Xi Tang; Yi-Zhou Cong; Shan-Cun Qu; Shi-Ju Luo; Guan-Pin Yang (Journal of Applied Phycology, 2007)

Allelopathic effects of Ulva pertusa, Corallina pilulifera and Sargassum thunbergii on the growth of the dinoflagellates Heterosigma akashiwo and Alexandrium tamarense - Renjun Wang; Hui Xiao; Peiyu Zhang; Liang Qu; Hengjiang Cai; Xuexi Tang (Journal of Applied Phycology, 2007)

Priorities for the conservation of avian biodiversity in China based on the distribution patterns of endemic bird genera - Fu-Min Lei; Yan-Hua Qu; Qian-Qian Tang; Shu-Cheng An (Biodiversity and Conservation, 2003)